Accurate prediction of wheat grain protein content via integration of genomic prediction and high-throughput phenotyping in breeding fields - Guoliang Wan; Lei Li; Luping Fu; Jixin Li; Boyang Xue; Shaolin Yan; Kai Wang; Zhiqiang Tao; Yonggui Xiao (Computers and Electronics in Agriculture, 2026)

Water management regulates vegetation recovery in photovoltaic farms across China - Yueran Hu; Junze Zhang; Xiaoming Feng; Gazi Salah Uddin; Lingfan Wan; Sitong Cai; Yue Guo; Bojie Fu (Land Use Policy, 2026)

Magnet-absorbed detrital magnetite from the western Qaidam Basin: Implications to Mars sample return missions - Qi-Tao Hu; Wen-Ping Liu; Qi-Zhi Yao; Shao-Bing Zhang; Wan-Cai Li; Sheng-Quan Fu; Yi-Liang Li; Gen-Tao Zhou (Icarus, 2026)

Improvement of myrtle wine quality by proline under tannic acid stress: Combined E-nose and HS-SPME-GC-MS analysis - Mengxiang Li; Yin Wan; Yanru Chen; Jingjing Liu; Haowei Fan; Mingjing Yi; Guiming Fu (Food Microbiology, 2026)

Genome-wide investigations of the lipid accumulation product index pinpoints polygenic determinants underlying pancreatitis susceptibility - Chia-Fu Chien; Zhengwei Qi; Zhengye Liu; Hanze Du; Ziqi Wan; Haotian Chen; Xiaoyin Bai; Jiarui Mi (Mammalian Genome, 2026)

Dihydrolipoamide dehydrogenase promotes hepatocellular carcinoma progression and modulates cuproptosis-dependent cell death - Mao-feng Zhong; Yu-yu Guo; Yuan Tian; Tian-xiao Zheng; Lu-yuan Zhu; Juan Du; Wan-fu Lin (Functional & Integrative Genomics, 2026)

Bioinspired orientation-regulated conductive hydrogels with hierarchical lamellar architecture for synergistic mechanical and electrical robustness - Tianhao Yu; Chao Rong; Ting Su; Shijia Wan; Bowei Zhang; Yabin Yan; Fu-Zhen Xuan (Chemical Engineering Journal, 2026)

Erratum to ‘Insights into the crucial role of clay minerals in the transport of gold nanoparticles through porous media’ [Applied Clay Science 290 (2026) 108250] - Wenqi Luo; Xin Nie; Zonghua Qin; Wenbin Yu; Yuhong Fu; Ping Zeng; Qi Sun; Meizhi Yang; Liang Chen; Quan Wan (Applied Clay Science, 2026)

Probiotics as a green strategy against Enterocytozoon hepatopenaei (EHP) in shrimp aquaculture: mechanisms and prospects - Runbo Li; Wenjun Shi; Hui Li; Libao Wang; Kuipeng Fu; Xihe Wan (Aquaculture, 2026)

Development of a frequency-domain wave load mapping methodology and its initial application to a 15 MW semi-submersible floating wind turbine - Shuijin Li; Rutian Wan; Yichao Lv; Ling Wan; Jie Fu; Ben He; Yulong Li; Torgeir Moan (Ocean Engineering, 2026)

O2 enhanced SF6 degradation in SiO2@TiO2 filled dielectric barrier discharge - Yalong Li; Zhe Huang; Kun Wan; Yangjing Le; Mingli Fu; Ying Zhang; Zhaodi Yang; Yan Luo; Xiaoxing Zhang (Journal of Environmental Chemical Engineering, 2026)

Highland barley polysaccharides promoted lactose intestinal fermentation in vitro: Unveiling the dynamic response of gut microbiota and polysaccharide structure - Jingyi Wang; Jiaxin Wei; Yuxuan Fu; Qinfei Wan; Jiayi Zhou; Kai Hu; Zisheng Han (Food Research International, 2026)

Optimized 3D hierarchical canopy Modeling of urban street trees for enhanced microclimate regulation - Yapeng Shao; Tailong Zhang; Xiaotong Fu; Youjun Liu; Hong Pan; Min Wan; Feng Qi; Yamei Shen (Energy and Buildings, 2026)

A dynamic adaptive electric field regulation strategy for stabilizing zinc anodes based on σ-electron donation - Hongxiang Zhao; Hua Yang; Jiayu Li; Yanwei Fu; Yu Zhao; Yuanshuai Wan; Yue Li; Yuliang Pang; Xingfa Qiu; Wenwen Duan; Weize Wang; Jiali Zhang; et al. (Chemical Engineering Journal, 2026)

Tailoring Cu-doped SmMn2O5 with rich Mn4+ active sites for highly efficient and selective ultra-low temperature photothermal NOx catalytic reduction - Mingxia Wu; Jiale Cheng; Yu Wang; Siying Zhang; Yi Li; Ruixue Bai; Chunming Yang; Lin Liu; Feng Fu; Jun Wan (Chemical Engineering Journal, 2026)

Non-denaturing fluorescence in situ hybridization: a transformative tool for chromosome identification and engineering for crop improvement in the plant genomics era - Chengzhi Jiang; Guangrong Li; Min Wan; Ennian Yang; Shulan Fu; Zongxiang Tang; Peng Zhang; Zujun Yang (Planta, 2026)

Comparative evaluation of fume suppressants for reducing hazardous emissions from asphalt binder: Mechanisms, efficiency, and rheological performance - Feng Ma; Jinshuo Yan; Ke Shi; Zhen Fu; Xinye Jiang; Ruizhe Huang; Shuo Wan; Tianyi Zhang (Transportation Research Part D: Transport and Environment, 2026)

Wetting-induced collapse of loess: Multistage microstructural evolution of particles and pores - Longlong Lv; Yaoxing You; Yukuai Wan; Yingpeng Fu (Transportation Geotechnics, 2026)

Rhizophagus intraradices differentially promotes growth and phosphorus uptake in Camellia oleifera under low versus adequate phosphorus supply - Wan-Lin Fu; Ying-Ning Zou; Shi-Qi Pu; Fang-Ling Wang; Zhi-Yan Xiao; Jun-Yong Cheng; Mei-Hua Yang; Mashael Daghash Alqahtani; Qiang-Sheng Wu (Rhizosphere, 2026)

Low-molecular-weight soybean peptides alleviate hyperuricemia in mice through xanthine oxidase inhibition, gut microbiota modulation, and metabolic reprogramming - Chen Wang; Jin Qian; Jiajing Liao; Lijuan Rao; Sen Mei; Bing Yuan; Tingting Geng; Haowei Fan; Guiming Fu; Yin Wan (Food Bioscience, 2026)

Corrigendum to “Associations between multiple metals exposure and cognitive function in the middle-aged and older adults from China: A cross-sectional study” [Environ. Res., 263(Pt 1), 2024, 120038] - Shiru Hong; Sheng Wu; Zhengce Wan; Chenming Wang; Xin Guan; Ming Fu; Chenliang Liu; Tianhao Wu; Guorong Zhong; Yuhan Zhou; Yang Xiao; Yingqian You; et al. (Environmental Research, 2026)

Balancing photovoltaic expansion with biocrust conservation in China's drylands: From spatiotemporal impact assessment to coupling-coordinated siting - Lingfan Wan; Yueran Hu; Yinqiu Ma; Bojie Fu (Environmental Impact Assessment Review, 2026)

Insights into the crucial role of clay minerals in the transport of gold nanoparticles through porous media - Wenqi Luo; Xin Nie; Zonghua Qin; Wenbin Yu; Yuhong Fu; Ping Zeng; Qi Sun; Meizhi Yang; Liang Chen; Quan Wan (Applied Clay Science, 2026)

Pressure and Permeability Evolution near Hydrate Exploitation Well During Constant-Rate Water Flooding: An Experimental Study - Yuning Liu; Yunkai Ji; Qiang Fu; Zhenyu Zhu; Zihao Wang; Gaowei Hu; Qiang Chen; Yongchao Zhang; Qingtao Bu; Yizhao Wan (Journal of Marine Science and Engineering, 2026)
Dynamic damage to the seepage characteristics of the near-well zone during natural gas hydrate exploitation is a key factor limiting production stability. There is still a lack of systematic understanding of the microscopic mechanisms underlying fine-particle migration and blockage in the near-well zone. In this study, a long sand-packed column was segmentally packed with clayey-silt sediments from the South China Sea and quartz sand to simulate the near-well reservoir and the packed layer, respectively. Long-term seepage processes in the near-well zone were simulated using water flow experiments at constant flow velocities. By combining pressure distribution monitoring with particle-size analysis, the spatiotemporal evolution of seepage characteristics in the near-well zone is revealed from both macroscopic and microscopic perspectives. Results indicate that under long-term displacement, the reservoir permeability near the injection end increased from 0.0149 mD to 0.0159 mD; the reservoir permeability near the packed layer exhibits the greatest decline, dropping from 0.0089 mD to 0.0065 mD. Combined with the particle-size analysis of the packer layer, the boundary between the reservoir and the packed layer is identified as the critical site for permeability damage in the near-well zone. Radial flow inversion shows that a reduction in wellbore radius leads to an increase in reservoir pressure, with the increase being greater the farther from wellbore. A decrease in the permeability of packed layer causes an increase in reservoir pressure, but the magnitude of the increase is consistent across different locations. It provides a theoretical basis for the optimized design of production wells.

Diosmetin alleviates retinal ischemia-reperfusion injury through SIRT1-mediated suppression of oxidative stress, inflammation, and PANoptosis - Peng Fu; Xiaobo Wan; Chunrong Zheng; Xiaonian Wu; Ke Xu; Qiuyu Lin; Minli Huang (Immunologic Research, 2026)

Nanomaterials as plant delivery carriers: transport mechanisms and design principles - Ye Li; Yezhuo Zhang; Zhun Zhang; Xi Zhang; Hongyang Wu; Man Zhang; Zhuo Li; Yinglang Wan; Yujie Fu; Wei Dong; Ruili Li; Jinxing Lin (Science China Life Sciences, 2026)

Experimental and numerical study of prefabricated bridge columns with UHPC-core socket connection - Jundong Fu; Zheng Lu; Tong Deng; Dianchao Wang; Shui Wan; Xilin Lu (Soil Dynamics and Earthquake Engineering, 2026)

Quantitative visualization of stress wave propagation and dynamic wave–interface coupling in faulted rock tunnels using 3D-printed photoelasticity - Yang Ju; Guoming Fu; Changbing Wan; Bofan Dai; Dongyi Xing (International Journal of Rock Mechanics and Mining Sciences, 2026)

A coupled elastoplastic damage subloading surface model for rock-like geomaterials subjected to triaxial cyclic compression - Jun Wu; Wei Wang; Ya-jun Cao; Shi-fan Liu; Wan-qing Shen; Jian-fu Shao (Computers and Geotechnics, 2026)

A synergistic metal ion–silane strategy enables fire-safe, water-repellent, and mold-resistant flattened bamboo board - Longchao Ma; Genmiao Wan; Yan Wang; Chenkai Dou; Danhe Liu; Yue Jiao; Hao Sun; Xinzhou Wang; Yi Chen; Qiliang Fu; Yanjun Li (Chemical Engineering Journal, 2026)

CircGABRB2_006 Drives Malignant Progression and EMT in Papillary Thyroid Carcinoma via the miR-296-5p/FGFR1 Axis - Chuan Wan; Yanjun Guo; Han Guo; Jingjing Zhu; Fangchao Liu; Yunyuan Zhang; Bingfei Cheng; Juanjuan Li; Ying Xin; Bingzi Dong; Weiwei Fu; Dongmei Meng; et al. (Biochemical Genetics, 2026)

Activating valence oscillations in reconstructed high-entropy selenide for self-stabilized seawater oxidation through localized lattice oxygen redox - Hai Li; Xiaoliang Zhang; Yangyang Liu; Taiping Fang; Xue Zou; Gui Wang; Shun Wan; Hongliang Dong; Zihao Lu; Yufan Wu; Jinhui Fu; Luobin Cao; et al. (Science Bulletin, 2026)

A regional hydrodynamic coefficient reconstruction workflow for internal-load recovery of a 15 MW semi-submersible floating wind turbine - Shuijin Li; Shuaibing Zhang; Ling Wan; Jie Fu; Ben He; Yibo Wang (Ocean Engineering, 2026)

The potential mechanism of nitrous oxide accumulation in wastewater treatment plants under different load conditions - Wen-Jiao Sang; Bing Gong; Chong-Yang Xing; Bei-Bei Chen; Zhi-Lin Zhang; Hui-Min Fu; Ya-Song Chen; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Yu-Lin Wang; Qiang Wang; et al. (International Biodeterioration & Biodegradation, 2026)

Aromatic vinegar-formulated Gardenia jasminoides Ellis extract alleviates hyperuricemia by remodeling gut microbiota, promoting SCFA production, and attenuating oxidative stress and renal injury - Xianchao Yi; Ziwen Xu; Yin Wan; Haowei Fan; Yulong Zhang; Jiayi Yuan; Chen Wang; Wenqing Cai; Xuehong Tian; Chaojun Liu; Guiming Fu (Food Bioscience, 2026)

Underestimation of industrial contributions to VOC fluctuation in the Hangzhou Bay: Insights from simultaneous measurements and ML-SHAP analysis - Kun Hu; Song Guo; Lei Shen; Zichao Wan; Xinshi Ni; Rui Tan; Xudong Tian; Bingye Xu; Limin Zeng; Qingyan Fu; Min Hu; Sihua Lu (Environmental Pollution, 2026)

Integrating P2/O3 intergrowth and Mg/Cu co-doping for highly stable sodium-ion battery cathodes - Canrong Cao; Weiliang Li; Zhiqiang Zhao; Jie Zhang; Mingbao Huang; Kai Wan; Zhiyong Fu; Zhenxing Liang (Chemical Engineering Journal, 2026)

Control of zeolite local microenvironment by organofluorination engineering toward efficient c-C4F8/C3F8 separation - Rui Sun; Zicheng Wan; Yaqi Wu; Yaohan Fu; Yang Zhang; Chenyang Yang; Heng Zhao; Ziqi Tian; Liang Chen (Chemical Engineering Journal, 2026)

Functional Characterization of CLE Peptides in Cotton Root Development Reveals GhCLE47 as a Key Regulator of Auxin-Mediated Root Architecture - Gai-Yuan Hu; Peng Liao; Xin-Yao Jiang; Ying-Chao Tang; Ting-Wan Li; Yang Li; Fu-Chun Xu; Zhen-Nan Zhang (Journal of Plant Growth Regulation, 2026)

Highly amphiphilicity-tailorable pineapple-like janus nanozymes with superior kinematic locomotion facilitates biphasic chemiluminescence analysis - Xin Jiang; Wan Wei; Yueming Zhao; Lingli Zhang; Wenwen Wang; Yuting Zhao; Zhongjie Zhu; Zhifeng Fu; Chengzhou Zhu; Hui Ouyang (Analytica Chimica Acta, 2026)

Optimisation and bioactivity evaluation of Brassica rapa L. seed oil extraction using novel green dimethyl ether extraction - Wan Xiao-Fu; Yimuranjiang Subuhati; He Tian; Miao-Miao Wang; Jia-Xin Yang; Le Pan; Mu-Chun Li (Natural Product Research, 2026)

Seismic dynamic response and sensitivity analysis of high-speed railway catenary systems under multidirectional excitations and traveling wave effects - Jin Chen; Qing-Bing Wan; Hao-Lin Xin; Bo Fu; Deliang Ma (Bulletin of Earthquake Engineering, 2026)

Chemical constituents from the stem of Nauclea officinalis and their anti-inflammatory activities - Bo Wen Wan; Ting Wang; Xiong Bo Zhu; Rui Hua Xu; Hao Fu Dai; Wen Li Mei; Fei Wu; Xiao Ying Peng; Sheng Zhuo Huang (Phytochemistry Letters, 2026)

Baculovirus manipulation of nutrient-based host choice via an infection responsive olfactory receptor in Spodoptera exigua - Zaiyuan Li; Xin Gao; Qihong Ma; Lianhai Fu; Changyou Li; Yan Shi; Jie Li; Qianlong Yu; Guiling Zheng; Chunhong Yang; Fanghao Wan; Wanqiang Qian; et al. (Pesticide Biochemistry and Physiology, 2026)

Investigating the mechanisms of motion response amplification for a cylindrical FPSO under wave-current coupling - Min Li; Da Li; Shenglei Fu; Yuan Zhuang; Decheng Wan (Ocean Engineering, 2026)

Mask-CDKD: A source-free and label-free cross-domain knowledge distillation framework from SAM for satellite onboard VHR land-cover mapping - Daoyu Shu; Zhan Zhang; Xiao Huang; Ru Wang; Nan Jia; Xinzhe Fu; Bingnan Yang; Fang Wan; Jianzhong Lu; Jianya Gong (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Investigation of fracture propagation mechanisms and inter-borehole superposition effects during liquid CO2 phase transition fracturing in coal seams - Yanbin Pei; Hongmin Yang; Wenlong Fu; Haiqing Zhang; Weifeng Shi; Shenqi Xiong; Shuchang Wan (Fuel, 2026)

From air to adipose: Investigating PM2.5-bound chlorinated paraffins and overweight/obesity in Chinese children and adolescents - Qi Yang; Hai-Xin Tu; Yu He; Ya-Qin Zhang; Muhammad Amjad; Jing-Fu Lai; Jing-Wen Huang; Yun-Ting Zhang; Wan-Ting He; Li-Xia Liang; Wen-Wen Bao; Yang Zhou; et al. (Environmental Research, 2026)

Wearable and breathable double-sided alginate/silk fibroin aerogel-nanofiber-based flexible sensor for personal thermal management and distinguishable multimodal sensing applications - Yu Fu; Peng Liu; Zhenshuai Wan; Ye Tian; Peng Wang; Chong Liu; Peng Sun; Shaoshuai Li; Dengjie Zhu; Caixia Ren (Chemical Engineering Journal, 2026)

λ-Carrageenan inhibits African swine fever virus infection potentially through its interaction with the viral envelope protein CD2v - Kun Han; Limeng Sun; Can Jin; Siqi Wan; Caiqin Cao; Yulu Yue; Man Lu; Xiaotong Wang; Yi Zheng; Hailong Liu; Yilin Guo; Dagang Tao; et al. (Carbohydrate Polymers, 2026)

A CRISPR/dCas9 mediated electrochemical impedimetric biosensor for sensitive mtDNA detection - Fei Chen; Mengqin Huang; Shu Zeng; Yi Wan; Anjun Qin; Xinzhe Yang; Danfeng Fu; Masoud Negahdary; Chenghui Zhang (Analytica Chimica Acta, 2026)

Microsphazaphilones H–Y: new azaphilone pigments with HIV latency reversal activity from the marine-derived fungus Microsphaeropsis arundinis P1B - Qing-Ren Lu; Xian-Yuan Yang; Lei Li; Lei-Ming Wu; Lu-Xiang Wan; Yi-Fan Fu; Xian-An Chen; Xin-Xiang Xu; Tao Yuan; Xin Chen; Abrar Ahmed; Nirmal Malik; et al. (Marine Life Science & Technology, 2026)

Analysis of the morphological structure and metabolic characteristics of Moniezia in sheep - Qian Mu; Wan-Ling Yao; Bao-Shan Wang; Wen-Zhu Chai; Fu-Hua Liu; Zhen Huang; Yong-Cheng Meng; Jing Pan; Xi-Ping Fan; Wan-Hong He; Wang-Dong Zhang (Veterinary Parasitology, 2026)

RlTTG1 isolated from Rosa laevigata Michx. regulates trichome development and stress response in transgenic Arabidopsis - Sinian Wu; Lisha Song; Yixi Chen; Cong Luo; Lingyun Wan; Guojian Liao; Wenjing Liang; Shugen Wei; Cuihong Yang; Yujian Huang; Ying Wei; Shixin Feng; et al. (Plant Science, 2026)

Complete and sequential reductive dechlorination of 1,2-dichloroethane and 1,2-dichloropropane by a Trichlorobacter-dominated consortium - Zhenghua Wu; Jixing Wan; Zijiao Zhang; Junao Jin; Hao Leng; Yulong Fu; Chaofeng Shen (Journal of Environmental Sciences, 2026)

Zircon evidence for exogenous water delivery to the lunar interior - Yong Wang; Xiao-Ping Xia; Jian Xu; Yong-Sheng Liu; Christopher J. Spencer; Trevor Ireland; Ze-Xian Cui; Xiao-Jia Zeng; Jan C.M. De Hoog; Aaron J. Cavosie; Bin Fu; Qing Yang; et al. (Earth and Planetary Science Letters, 2026)

Ultrasound-activated in situ nano-vaccines (SATNAV) for precise CRPC sono-immunotherapy via multi-reprograming the immunosuppressive microenvironment - Xinzhi Xu; Jing Fu; Yujie Wan; Jiaqi Gong; Ruixia Hong; Jia Tang; Qizhi Wang; Ying Li; Kaifeng Huang; Yizhe Zhong; Hang Zhou; Jichun Yang; et al. (Chemical Engineering Journal, 2026)

Open spatial relation extraction about geological objects with dependency graph network - Deping Chu; Lele Fu; Bo Wan; Fang Fang; Shunping Zhou (Earth Science Informatics, 2026)

Seasonal temperature rise influences nitrous oxide and methane accumulation in freshwater habitats via distinctive microbial processes - Teng-Fei Ma; Wen-Ke Liu; Chong-Yang Xing; Ya-Song Chen; Hui-Min Fu; Ji-Chun Bai; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Meng-Wen Peng (Environmental Pollution, 2026)

Corrigendum to “Multi-crosslinked hydrogel built with hyaluronic acid-tyramine, thiolated glycol chitosan and copper-doped bioglass nanoparticles for expediting wound healing” [Carbohydrate Polymers 327 (2024) 121635] - Yifeng Yu; Congcong Wang; Qiaoqin Fu; Ying Wan; Aixi Yu (Carbohydrate Polymers, 2026)

Unveiling the mechanisms of mechanical stirring for enhanced performance and stability of algal-bacterial flocs treating low C/N synthetic wastewater - Jun-Jie Gu; Bin-Di Mao; Xiao-Xiao Dou; Bin-Xin Zhang; Jia-Wei Xu; Chun-Wan Fu; Bang-Jie Lan; Xin-Jie Zhang; Zhe Xu; Feng Gao (Bioresource Technology, 2026)

Impact of different mixing temperature on the microstructural evolution and properties of metakaolin-based geopolymers - Xiuqiong Fu; Qian Wan; Yong Fan; Yimin Zhang; Ruobing Zhang (Applied Clay Science, 2026)

Magmatic–hydrothermal mineralization processes in the Xiwukou Sn–W–Rb deposit, Jiangnan orogenic belt: Constraints from multi-mineral U–Pb geochronology - Kun-Yan Wu; Xiao-Ying Gao; Qi Hou; Xiao-Yong Yang; Qiu Wan; Xiang Qian; Fu-Jun Zhong; Gen-Tao Zhou (Mineralium Deposita, 2026)

Utilization of synthetic minority oversampling technique and transfer learning for improving rice and wheat LAI estimation - Ziheng Feng; Ke Wu; Bo Xu; Haiyan Cen; Yuan Zhang; Xiangtai Jiang; Hanyu Xue; Heguang Sun; Hao Yang; Haikuan Feng; Huiling Long; Xingang Xu; et al. (Computers and Electronics in Agriculture, 2026)

Integrative transcriptomic and epigenomic analysis reveals the molecular mechanism of light-enhanced calcification in giant clams - Wenjie Yi; Fan Mao; Ke Wan; Shiwei Fu; Md. Abu Kawsar; Xiangcheng Yuan; Jun Li; Zhiming Xiang; Shu Xiao; Weihua Zhou; Ziniu Yu; Yang Zhang (Aquaculture, 2026)

Hyphosphere metabolic reprogramming in lipids and aromatic amino acids drives differential mycorrhizal growth promotion in trifoliate orange - Hao-Ran Jiang; Wan-Lin Fu; Ci Deng; Ying-Ning Zou; Mashael Daghash Alqahtani; Qiang-Sheng Wu (Rhizosphere, 2026)

From resistance to detection: The role of nanomaterials in plant stress responses - Jing-wan Zhang; Rui-Rui Hao; Abolghassem Emamverdian; Wen-Xun Su; Xing-Hao Zhang; Meisam Zargar; Mo-Xian Chen; Fu-Yuan Zhu (Plant Science, 2026)

Long-term evidence that controlled-release urea enhances yield and soil fertility while mitigating environmental impacts in double-season rice - Yifan Fu; Wei Yang; Meng Zhang; Xiangning Wu; Guodong Yang; Hongshun Xiang; Chanchan Du; Jinjuan Zhu; Chen Yang; Yunfan Wan; Shaobing Peng; Yu’e Li; et al. (Field Crops Research, 2026)

Epidemiology of Isoparorchis eurytremus (Trematoda: Isoparorchiidae) Infection in Southern Catfish (Silurus meridionalis; Siluriformes: Siluridae): A Case Study in the Dongting Lake, China - Dong Liu; Xiangrong Liu; Mingjun Yan; Naige Fu; Wei Wan; Gang Xu; Qianqian Ku; Xin Yang; Bo Hong; Chongrui Wang; Dongsheng Ou; Xiping Yuan (Fishes, 2026)
Parasitic infections pose a significant threat to the wild population of Southern catfish (Silurus meridionalis) in Dongting Lake, yet the specific pathogen identity and epidemiological drivers remain unclear. This study combined morphological assessment, 28S rDNA molecular identification, and Generalized Linear Models (GLM) to elucidate the infection dynamics and pathogenicity of trematodes. Molecular analysis confirmed the pathogen as Isoparorchis eurytremus. GLM analysis revealed that apparent spatiotemporal variations in infection were actually sampling bias in fish host size structure; the total length was identified as the decisive predictor of infection risk. The infection probability followed a sigmoid growth pattern with a median infection length (L50) of 70.4 cm, a phenomenon attributed to the host’s ontogenetic diet shift from insectivory to obligate piscivory. Anatomical observations indicated that the infection induced systemic pathology; beyond severe fibrosis and mechanical damage to the swim bladder, varying degrees of parenchymal lesions were evident in the liver, spleen, and kidney. These findings indicate that I. eurytremus infection in S. meridionalis is a size-dependent, accumulative process maintaining a homogenous high pressure across the lake ecosystem, necessitating a shift in perspective from localized lesions to systemic disease management.

Development and characterization of monoclonal antibodies targeting the major capsid protein (MCP) of scale drop disease virus (SDDV) - Yuting Fu; Jianfei Wan; Wenfeng Zhang; Yong Li; Jianguo He; Chuanfu Dong (Aquaculture, 2026)

Experimental investigation on buried pipeline bending deformation monitoring using flexible piezoelectric sensing - Jun Wang; Lipeng Wan; Kai Chen; Tong Zhang; Zhiming Liu; Zhouxia Fu; Junfeng Ni; Ziyang Gao; Hongtao Fu (Tunnelling and Underground Space Technology, 2026)

Proanthocyanidin B2 regulates epidermal growth factor receptor (EGFR) and activates the PI3K/AKT pathway to promote the in vitro maturation of sheep oocytes - Yucheng Liu; Jingjing Wang; Zhenliang Zhang; Jiachen Bai; Houru Li; Zhanmin Lv; Lei Gao; Jianhong Ni; Shouliang Lu; Changbin Liu; Guiping Hai; Weijun Liu; et al. (Theriogenology, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

An enhanced sorting method for second-life lithium-ion batteries based on two-step clustering - Fu Wan; Yupeng Lin; Da Yang; Shufan Li; Ruiqi Liu; Lei Zhu; Wenwei Yin; Weigen Chen (Journal of Cleaner Production, 2026)

Engineering optimization of food waste treatment via anaerobic digestion: Building causal machine learning networks for comprehensive analysis - Fangyun Wang; Yi Zhang; Jianfeng Peng; Yu Fu; Hao Wan; Jinling He; Jianping Su; Yanjuan Lu; Yeqing Li (Journal of Cleaner Production, 2026)

Direct co-extraction of nickel and cobalt from sulfuric acid leachate of laterite ore using extractant DY319 in kerosene followed by impurity removal using D2EHPA to produce high purity mixed concentrated solution - Situmeang Elfrida Margaretha; Wenjing Wan; Wenjuan Guan; Mingbo Fu; Yanni An; Qinggang Li (Hydrometallurgy, 2026)

A novel pathologic scoring system for predicting postoperative recurrence in BCLC stage 0-A hepatocellular carcinoma patients: a nationwide multicenter study - Feng Xia; Jing Yan; Xulin Liu; Zhao Huang; Zhancheng Qiu; Qiao Zhang; Zhenheng Wu; Zhiyuan Huang; Renjie Wei; Li Lin; Liping Liu; Shuangqin Han; et al. (Science China Life Sciences, 2026)

Automated measurement of optic nerve sheath diameter using ocular ultrasound video - Renxing Li; Weiyi Tang; Peiqi Li; Qiming Huang; Jiayuan She; Shengkai Li; Haoran Xu; Yeyun Wan; Jing Liu; Hailong Fu; Xiang Li; Jiangang Chen (Medical & Biological Engineering & Computing, 2026)

An instantaneous and reliable precise point positioning integer ambiguity resolution method based on multistage residual tests - Yuan Tian; Xiaopeng Gong; Fu Zheng; Chuang Shi; Jiale Wang; Lihua Wan (GPS Solutions, 2026)

Spatial source apportionment of n-alkanes and their effects on carbon pool dynamics and microbial communities in a river–estuary–offshore continuum - Jingyi Xu; Qiang Fu; Kaichao Wan; Fujun Shi; Weidong Wang (Water Research, 2026)

CsNAC73 promotes cold-induced theanine biosynthesis by activating CsAlaDC expression in albino Camellia sinensis cv. Baiye 1 - Dandan Li; Ying Sun; Xin He; Xin Cheng; Maoyin Fu; Xuchun Zhang; Qi Chen; Xiaochun Wan; Linlin Liu (Plant Science, 2026)

Influence of pyrolysis on biomass structure: microscopic deformation patterns and chemical composition variations - Shao-Hua Sun; Jiang Wan; Hui-Chun Fu; Yong-Huan Sun; Feng Shao; De-Sen Ni; Jian-Jiang Lu (Fuel, 2026)

Plant-based edible emulsion gels from rye secalin for 3D-printed fat mimetics - Siyong You; Weitong Wen; Yuhan Wan; Lingshan Su; Shunjiang Zeng; Yan Kong; Caili Fu; Dejian Huang; Linzhi Jing (Food Research International, 2026)

Effects of galactomannan on the quality and component structure of hot-dry noodles during freeze-thaw cycles - Liuyu Wan; Yang Fu; Zhonghua Yuan; Peili Lin; Nian Cheng; Shensheng Xiao; Wenping Ding; Xuedong Wang (Food Chemistry, 2026)

Application of nano-selenium and glutathione with pyrimethanil enhance cucumber resistance to Botrytis cinerea by boosting root secretion and recruiting beneficial microorganisms - Yujiao Jia; Lu Kang; Ping Wang; Tong Wu; Xiaorui Fu; Xiaoying Wan; Tingjie Huang; Xiangzhong Wei; Xi Wang; Yaling Bi; Canping Pan (Chemical Engineering Journal, 2026)

Physics-based unified formulation for predicting clear-water equilibrium scour depth and scour threshold velocity around piles - Wen-Gang Qi; Biao Li; Shun-Yi Wang; Yong Wan; Pei-Qing Zhao; Fu-Ping Gao (Coastal Engineering, 2026)

Byakangelicol Alleviates Ischemic Brain Injury by Inhibiting Microglial Activation and Oxidative Stress - Xiao Wan Wang; Yan Qiong Fu; Zhuo Li Li; Ting Li; Hui Lan Wang; Yu Zheng; Chan Zhang; Miaolin Zeng; Chan Li; Dewei Xie; Bai Hui Chen (Molecular Neurobiology, 2026)

A novel arithmetic operation function utilizing height of interval type-2 fuzzy sets to express risk preference: case study of remotely controlled autonomous ship - Cunlong Fan; Yongquan Chen; Shiqi Fan; Shanshan Fu; Chengpeng Wan; Yongtao Xi; Zaili Yang (Ocean Engineering, 2025)

Mussel-inspired coating anchored polyquaternium functionalized nonwoven fabrics for microplastic adsorption - Yuanshuai Wan; Yanjun Jia; Yonggui Guo; Jianteng Sun; Maofeng Liang; Lichao Gao; Haidong Cao; Tiantian Liu; Hongxiang Zhao; Yuliang Pang; Yanwei Fu; Yu Zhao; et al. (Journal of Environmental Chemical Engineering, 2025)

Sustainable recycling of spent graphite anodes: The critical role of thermal-assisted organic acid leaching in structural and performance restoration - Fu Wan; Wenwei Yin; Da Yang; Kaida Hu; Ruiqi Liu; Yupeng Lin; Weigen Chen (Journal of Environmental Chemical Engineering, 2025)

Multifunctional trilayer films based on gelatin-dextran incorporated with defatted rice bran-derived carbon dots for scallop preservation - Hongkai Xie; Hailu Liao; Xinhao Wan; Yinlei Mao; Fengjiao Fan; Yuhong Fu; Li Wang; Liwei Mao; Yan Li; Zhuoli Li (Food Chemistry, 2025)

Logging intensity and biome type mediate the effects of forest logging on soil greenhouse gas emissions - Chenjun Du; Xing Wu; Hao Shi; Bojie Fu; Ting Li; Yihe Lü; Lingfan Wan; Shuang Zhang; Binbin Huang; Yibin Shi (Agriculture, Ecosystems & Environment, 2025)

Cover Image - Yuting Fu; Can Mao; Jianfei Wan; Qianqian Sun; Fangzhao Yu; Jie Sun; Jiang Wu; Yong Li; Chuanfu Dong (Journal of Fish Diseases, 2025)

Detection and Genomic Characterisation of Scale Drop Disease Virus (SDDV) in Farmed Yellowfin Seabream ( Acanthopagrus latus ) in Southern China - Yuting Fu; Can Mao; Jianfei Wan; Qianqian Sun; Fangzhao Yu; Jie Sun; Jiang Wu; Yong Li; Chuanfu Dong (Journal of Fish Diseases, 2025)
Scale drop disease virus (SDDV) is a distinct member of the genus Megalocytivirus within the family Iridoviridae , which was recently identified as a causative agent of yellowfin seabream Acanthopagrus latus ascitic diseases (YFSBAD). Here, a molecular surveillance of SDDV in pond‐cultured yellowfin seabream was conducted during 2021 to 2023 in Zhuhai, the most significant breeding region for this fish species in China. A total of 73 batches of naturally diseased yellowfin seabream samples were collected for SDDV detection. As a result, 31 samples were confirmed SDDV positive by conventional PCR detection, among which 9 additional SDDVs were isolated by using MFF‐1 cell line, and 4 isolates were further validated by monoclonal antibody‐based immunofluorescence assays. Multiple alignment and phylogenetic analysis revealed that these isolates shared the identical mcp sequences and were clustered within the same clade. Additionally, the complete genome sequence of a new SDDV isolate (SDDV‐ZH918/23) was determined and annotated. The result shows that SDDV‐ZH918/23 consists of 131,741 bp and encodes 143 putative open reading frames. The genome collinearity analysis demonstrated very high nucleotide similarity among all SDDV isolates distributed in China and other Asian countries. Unexpectedly, a 152 bp deletion mutant was also found in two SDDV isolates. Collectively, our study once again demonstrates that SDDV acts as an emerging etiological agent in farmed yellowfin seabream, and a partial deletion mutant of the SDDV genome was first recorded.

First demonstration of spaceborne L-band bistatic single-polarization single-baseline SAR interferometry on the retrieval of forest vertical structural information - Yang Lei; Weiliang Li; Yanghai Yu; Xiaotong Liu; Jie Xu; Anmin Fu; Jie Wan; Changcheng Wang; Wenli Huang; Zixuan Qiu; Tao Li; Haiqiang Fu; et al. (Remote Sensing of Environment, 2025)

Risk analysis of passenger ships in a mixed traffic environment: a case study of the Huangpu River - Yong Zhou; Xinyu Shen; Shanshan Fu; Yang Zhang; Hui Wan (Ocean Engineering, 2025)

Impact of altered quartz surface chemistry on mechanical properties and microstructure of geopolymers - Xiuqiong Fu; Qian Wan; Yong Fan; Yimin Zhang; Ruobing Zhang; Zhijie Guo (Environmental Research, 2025)

Revealing the role of Fe particle size in soft magnetic geopolymer for enhancing energy conversion in airport pavement induction heating - Gonghui Gu; Xinchi Xu; Jinsheng Han; Lin Wan-Wendner; Zhiji Gao; Rongze Fu; Chuanqing Fu; Tao Ma (Energy and Buildings, 2025)

A directional freezing synergistic “non-solvent quenching" strategy for fabricating high-performance gel for soft electronics - Xie Fu; Ziwei Pan; Lei Wan; Lyes Douadji; Wenqiang Lu; Xingzhan Wei (Chemical Engineering Journal, 2025)

Single nucleotide polymorphisms of the Waxy gene and their relationship with the physicochemical properties of Pueraria lobata (kudzu) starch - Ruiqi Zha; Ying Fan; Yuhao Fu; Chunyan Liu; Haoliang Sun; Jiaxin Wan; Min Wei; Zhixing Jin; Peng Li; Zhongyan Zhu; Jing Wei; Jun Yin; et al. (Carbohydrate Polymers, 2025)

Development and characterization of phosphate tailings-based humic acid slow-release fertilizer using ball milling sludge acid activation - Yinxin Xie; Qi Zhang; Deyi Yuan; Yingjie Hu; Caiyuan Guo; Muhammad Atif Muneer; Yafu Tang; Yanhui Xu; Fu Wan; Youzhi Yang (Process Safety and Environmental Protection, 2025)

Middle Campanian to Maastrichtian foraminifera and biomarkers: Seawater incursion events in the Songliao Basin, Northeast China - Ke-Ying Yue; Sha Li; Tian Jiang; Dang-Peng Xi; Bo-Wen Song; Yu Liang; Li-Xin Sun; Tian-Fu Zhang; Hai-Chun Zhang; Xiao-Qiao Wan; Bo Wang (Palaeoworld, 2025)

Algal-bacterial symbiosis strengthens the treatment of high-salinity phenolic wastewater and its molecular mechanism - Xiao-Xiao Dou; Bin-Di Mao; Ang Li; Jun-Jie Gu; Xiao-Ling Zhang; Chun-Wan Fu; Xin-Jie Zhang; Bang-Jie Lan; Jia-Wei Xu; Bin-Xin Zhang; Hong-Jie Zheng; Feng Gao (Journal of Hazardous Materials, 2025)

Salmon leather collagen peptide alleviates UVA-induced photoaging via Nrf2/Keap1 pathway by enhancing antioxidant defense and preserving skin elasticity - Baifeng Fu; Yu Wan; Xiaoyu Ma; Zhihui Chang; Ximing Yang; Xinran Liu; Haixia Wu; Shuzhen Cheng; Ming Du (Food Bioscience, 2025)

Ultra-fine palladium‑gold alloy nanoclusters anchored on amino-grafted self-pillared pentasil zeolite for efficient dehydrogenation of formic acid - Shiyu Wan; Guangying Fu; Dongyan Xu; Peng Lu; Valentin Valtchev (Chemical Engineering Journal, 2025)

Synergistic catalysis of CuxFey/CeO2 bimetallic catalysts for oxidative dehydrogenation of C2H6 with CO2 - Dan Guo; Zouxuan Qi; Zelong Fu; Zhenli Lv; Li Kang; Feigang Zhao; Tongrui Wan; Shengping Wang; Xinbin Ma (Chemical Engineering Journal, 2025)

Unveiling entropy on electrocatalysis performances based on precise-manipulated medium-entropy alloy aerogels - Lanqing Li; Chao Fu; Xiufang Zhu; Xinhao Wan; Jianqi Ye (Chemical Engineering Journal, 2025)

Wearable multimodal flexible sensor based on layer-by-layer aerogel/nanofibers composite structure for real-time information encoding and gesture recognition - Zhenshuai Wan; Peng Liu; Yu Fu; Yibin Fan; Shun Peng; Chengqian Zhang; Ye Tian; Shuangkun Wang; Longwang Yue; Ronghan Wei (Chemical Engineering Journal, 2025)

Impact of SNP Variants in PON-1 or UGT1A1 on Iron Chelation Therapy Outcomes and Zinc Status in Thalassemia Major Patients - Meng-Yao Lu; Wan-Fu Tsai; Chang-Shiann Wu; Chien-Sheng Wang; Nailis Syifa; Mong-Liang Lu; Jiahn-Haur Liao; Wei J. Chen; Kai-Hsin Lin; Tzu-Hua Wu (Biological Trace Element Research, 2025)

Lipid droplet clearance inhibits esophageal cancer growth via metabolic reprogramming - Yan Pu; Yi Wan; Yuhua Fu; Kai Li; Yijiao Chen; Yunzhi Wang; Bin Li; Lingling Li; Zhaoyu Qin; Jingyan Xu; Dongxian Jiang; Yan Li; et al. (Science Bulletin, 2025)

Anti-inflammatory abietane-type diterpenoids from the roots of Salvia przewalskii - Yan-Fang Chen; Yu-Qing Lu; Wan-Yun Gao; Bo-Yi Fan; Fu-Cai Ren; Chuan-Pu Shen (Phytochemistry, 2025)

Bisphenol A caused abnormal spermatogenesis of Eriocheir sinensis through es-ERR/es-KIF4A pathway with discussion of BPA substitutes - Yu Yang; Di Wu; Tian Lei; Hang-Yuan Zhao; Jun-Jie Yu; Lan-Min Wang; Ding-Xi Liu; Yan-Shuang Zhao; Jia-Hao Ni; Fu-Qing Tan; Wan-Xi Yang (Journal of Hazardous Materials, 2025)

Future water stress in China: Projections under socioeconomic and climate change scenarios - Danyang Gao; Guangtao Fu; Xi Wan; Fayyaz Ali Memon (Journal of Environmental Management, 2025)

Integrated transcriptomic and physiological and biochemical analysis reveal the molecular mechanism of proline regulating the resistance of Saccharomyces cerevisiae to tannic acid stress - Mengxiang Li; Yin Wan; Haowei Fan; Jingjing Liu; Wenqin Cai; Jiayi Yuan; Hao Wang; Guiming Fu (Food Bioscience, 2025)

Life cycle assessment and optimization scenarios of sofas: a case study in China - Ruiying Wan; Xianqing Xiong; Sijie Fu; Dejun Xiong; Xiutong Xu (The International Journal of Life Cycle Assessment, 2025)

The long-term environmental evolution of an urban lake in the highly developed Yangtze River Delta - Zhenglan Fu; Longjuan Cheng; Qingfeng Jiang; Jiali Zhang; Xinyue Chen; Shuyi Yang; Xinyuan Gao; Xiang Kuai; Dejun Wan; Dongliang Ning; Bin Xue (Journal of Geographical Sciences, 2025)

Contributions of natural and anthropogenic factors to summertime thermal environments across different urban scales: An investigation in Chengdu-Chongqing agglomeration, China - Yangtao Wan; Song Yang; Han Han; Yao Mao; Xiao Liu; Meizi You; Xuecheng Fu; Junqing Tang; Ali Cheshmehzangi; Leila Mohaghegh Zahed; Bao-Jie He (Environmental Impact Assessment Review, 2025)

The Role of Complement C1qa in Experimental Intracerebral Hemorrhage - Xiongjie Fu; Fenghui Ye; Yingfeng Wan; Guohua Xi; Ya Hua; Richard F. Keep (Translational Stroke Research, 2025)

Electroacupuncture regulates the P2X7R-NLRP3 inflammatory cascade to relieve decreased sensation on ocular surface of type 2 diabetic rats with dry eye - Mi-Mi Wan; Zhang-Yitian Fu; Tuo Jin; Zhuo-Yuan Wang; Xin-Yi Sun; Wei-Ping Gao (Purinergic Signalling, 2025)

Discovery of large-scale natural hydrogen leakage in the Zhangbei Basin, North China - Jianliang Jia; Minjie Lu; Bingchuan Yin; Zhuangwei Luo; Ling Liu; Qianning Tian; Gang Fu; Yanming Liu; Yanming Wan; Huiqun Yang (Science Bulletin, 2025)

Rapid evaluation of Curcuma origin and quality based on E-eye, flash GC e-nose, and FT-NIR combined with machine learning technologies - Qiang Guo; Ming-xuan Li; Rao Fu; Xin Wan; Wen-hao Dong; Chun-qin Mao; Zhen-hua Bian; De Ji; Tu-lin Lu; Yu Li (Food Chemistry, 2025)

In situ constructing artificial interfacial layer enables dendrite-free zinc anode in aqueous batteries - Canglong Li; Changding Wang; Jie Huang; Qiwen Zhao; Wen Liu; Yuxuan Song; Mingjun Rao; Fu Wan; Yuejiao Chen; Weigen Chen; Shuhui Sun (Chemical Engineering Journal, 2025)

Myocardial infarction serum preconditioning bone marrow mesenchymal stem cell-derived exosomes enhance anti-fibrosis in rat myocardial infarction hearts - Yang Gan; Changyi Wang; Ruili Liao; Pei Zhang; Yongmei Nie; Fengxu Yu; Juyi Wan; Bin Liao; Liang Mao; Hui Liu; Yong Fu (Molecular and Cellular Biochemistry, 2025)

The significance of organophosphate flame retardants in patients with esophageal squamous cell carcinoma - Hung-I Lu; Wan-Ting Huang; Wen-Chin Lee; Fu-Jen Cheng; Chia-Te Kung; Chin-Chou Wang; Liang-Jen Wang; Yu-Che Ou; Shau-Hsuan Li (Environmental Geochemistry and Health, 2025)

Coordinated development of land use change and habitat quality in the border mountainous area of China: A multi-scenario perspective - Wenqiang Wan; Xinmin Zhang; Xiao Zhou; Tiangui Lv; Guoliang Xu; Shuai Fu (Environment, Development and Sustainability, 2025)

High-throughput maize seed ears sorting through structural re-parameterisation classification model and multi-channel sorting system - Xiang Ma; Yonglei Li; Lipengcheng Wan; Zongtian Liu; Jinyu Song; Xiaopei Zheng; Qiufeng Fu (Biosystems Engineering, 2025)

Occurrence, spatial-seasonal variation and air-soil exchange of traditional and novel organochlorine pesticides across 30° latitude in Eastern China: Old tales and new realities - Liang Wang; Wan-Li Ma; Pu-Fei Yang; Chun-Yan Huo; Peng-Tuan Hu; Wen-Long Li; Meng-Qi Fu (Journal of Hazardous Materials, 2025)

Untargeted metabolomics and network pharmacology reveal the uric acid-lowering effects of alcohol extract of Gnaphalium affine and its extracts in hyperuricemic rats - Chen Wang; Xinchao He; Lijuan Rao; Jiajing Liao; Jin Qian; Xuefeng Yu; Sen Mei; Suqin Lin; Linqian Xu; Guiming Fu; Yin Wan (Food Bioscience, 2025)

Breeding of lactic acid-tolerant Saccharomyces cerevisiae based on atmospheric and room temperature plasma technology and automatic high-throughput microbial microdroplet culture system - Haowei Fan; Yin Wan; Yixin Huang; Jayi Yuan; Jiahui Fan; Yaru Kou; Xuefeng Yu; Yufeng Pan; Dan Huang; Guiming Fu (Food Microbiology, 2025)

In situ multifunctional gel for hormone-immune therapy of ovarian cancer and prevention of postoperative adhesion - Yankun Zhang; Yanbin Shi; Hengchang Zang; Xiaogang Zhao; Xianglei Fu; Shengnan Qiu; Yuan Zhang; Yingying Liu; Xiaoyu Wan; Zengmei Li; Yaqi Li; Jiamin Zhou; et al. (Chemical Engineering Journal, 2025)

Deep eutectic solvents for ginsenoside extraction and inhibition of ginsenoside hydrolysis in Panax notoginseng leaves: methodology and mechanistic insights - Jia-Yue Liu; Shi-Yao Hua; Li-Juan Ma; Xin Tao; Wen-Yu Fu; Jian-Bo Wan (Chemical Engineering Journal, 2025)

Hybrid Path Planning Method for USV Based on Improved A-Star and DWA - Yan Liu; Zeqiang Sun; Junhe Wan; Hui Li; Delong Yang; Yanping Li; Wei Fu; Zhen Yu; Jichang Sun (Journal of Marine Science and Engineering, 2025)
This paper presents a hybrid path planning method that integrates an enhanced A-Star algorithm with the Dynamic Window Approach (DWA). The proposed approach addresses the limitations of conventional A-Star algorithms in global path planning, particularly their inability to adaptively avoid obstacles in real-time. To improve navigation safety, the A-Star search strategy is enhanced by avoiding paths that intersect with obstacle vertices or pass through narrow channels. Additionally, a node optimization technique is introduced to remove redundant nodes by checking for collinearity in consecutive nodes. This optimization reduces the path length and ensures that the path maintains a safe distance from obstacles using parallel lines. An advanced Bézier curve smoothing method is also proposed, which adaptively selects control points to improve path smoothness and driving stability. By incorporating these improvements, the enhanced A-Star algorithm is combined with DWA to facilitate dynamic obstacle avoidance while generating global paths. The method accounts for the kinematic characteristics of the USV, as well as physical constraints such as linear and angular velocities, enabling effective handling of obstacles in dynamic environments and ensuring safe navigation. Simulation results demonstrate that the proposed algorithm generates secure global paths, significantly optimizing node count, path length, and smoothness, while effectively avoiding dynamic obstacles, thus ensuring safe navigation of the USV.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Effectiveness and mechanism of using sodium alginate-magnesium silicate carrier in UASB reactor to resist shock loading of coking wastewater - Yi Jiang; Wenlai Xu; Yizhi Zhang; Ruoxi Yan; Yifei Xie; Dan Zhang; FengLin Jia; Linshan Yang; Shah Zaib; Ruiyang Li; Pan Li; Songyu Fu; et al. (Journal of Cleaner Production, 2025)

A critical review of human internal exposure to short-chain chlorinated paraffins and its concerning health risks - Ke Fang; Yi-bin Sun; Run-ming He; Jian-kun Qian; Wen Gu; Yi-fu Lu; Zhao-min Dong; Yi Wan; Chao Wang; Song Tang (Environmental Research, 2025)

Associations of welding-related metals and hypertension in male welders: Roles of cytokinesis-block micronucleus cytome assay parameters - Xiayun Dai; Fan Wang; Yonggang Liao; Na Tu; Xiaolei Fu; Wenjuan Fu; Yizhe Sun; Junpin Liu; Siyu Wan; Wenjun Yin; Wei Pi; Jiaojun Liang; et al. (Environmental Pollution, 2025)

Dietary pyridoxine promoted muscle protein deposition relating to PI3K/AKT/TOR pathway and the ubiquitin proteasome system in grass carp (Ctenopharyngodon idella) - Li-Fu Gong; Xiao-Qiu Zhou; Lin Feng; Pei Wu; Wei-Dan Jiang; Yao-Bin Ma; Xiao-Wan Jin; Hong-Mei Ren; Jia-Yong Tang; Fa-Li Wu; Yang Liu (Food Bioscience, 2025)

Robust Zn metal anode by a Ti3C2T MXene/acrylonitrile–butadiene–styrene terpolymer composite coating - Jidong Hu; Yali Li; Xiaoyang Liu; Yunxia Dong; Guodong Wan; Yongchao Chen; Donghao Li; Hongyun Ma; Xiaodi Du; Yujun Fu; Deyan He; Junshuai Li (Chemical Engineering Journal, 2025)

Chemical constituents of Xylanche himalaica and their chemotaxonomic significance - Wei Nie; Li-Ping Feng; Jin-Fu Wan; Xiao-Hui Li; Ying-Jie Zhang; De-Huan Fu; Qian Li (Biochemical Systematics and Ecology, 2025)

Improving forecast of “21.7” Henan extreme heavy rain by assimilating high spatial resolution GNSS ZTDs - Mengjie Liu; Yidong Lou; Weixing Zhang; Rong Wan; Zhenyi Zhang; Zhikang Fu; Xiaohong Zhang (Atmospheric Research, 2025)

Deep Learning Imaging-Based Reconstruction Improved the Image Quality of Synthetic High B-Value DWI for Prostate Lesion Detecting - Xiuxiu Zhou; Hanxiao Zhang; Song Jiang; Jiankun Dai; Lingling Gu; Pei Zhang; Ye Fu; Jie Shi; Xinyi Wan; Meiling Xu; Shiyuan Liu; Li Fan (Journal of Medical and Biological Engineering, 2025)

Application of Unmanned Aerial Vehicle Remote Sensing on Dangerous Rock Mass Identification and Deformation Analysis: Case Study of a High-Steep Slope in an Open Pit Mine - Wenjie Du; Qian Sheng; Xiaodong Fu; Jian Chen; Jingyu Kang; Xin Pang; Daochun Wan; Wei Yuan (Journal of Earth Science, 2025)

Nuclear receptor coactive 4-mediated ferritinophagy: a key role of heavy metals toxicity - Wan-Xue Xu; Xue Wen; Yi-Tong Fu; Jie Yang; Han Cui; Rui-Feng Fan (Archives of Toxicology, 2025)

mtNET-mineral complex: a building block of calculus - Yutong Fu; Meichen Wan; Yina Zhu; Dongxiao Hao; Qianqian Wan; Wen Niu; Zhaoyang Ren; Kehui Xu; Weijun Qin; Shiren Sun; Wei Yi; Kai Jiao; et al. (Science Bulletin, 2025)

Tanshinone IIA mitigates postoperative cognitive dysfunction in aged rats by inhibiting hippocampal inflammation and ferroptosis: Role of Nrf2/SLC7A11/GPX4 axis activation - Yan Yang; Bo Wang; Yichen Jiang; Wan Fu (NeuroToxicology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Antimicrobial perylenequinones isolated from the endophytic fungus Alternaria alstroemeriae - Yong-Fu Li; Fang Yue; Xu-Ri Wan; Chang Li; Yi Sun; Yue-Hu Pei (Phytochemistry Letters, 2025)

Nondestructive three-dimensional structure and growth characteristics of anammox granular sludge - Meng-Wen Peng; Ya-Song Chen; You-Peng Chen; Wan Sun; Meng-Meng Liu; Xun Weng; Shuai Wang; Yu Shen; Hui-Min Fu (International Biodeterioration & Biodegradation, 2025)

Role of the clock gene period in regulating circadian rhythm of courtship vibrations in Nilaparvata lugens - Qi Wei; Jia-Chun He; Wei-Xia Wang; Feng-Xiang Lai; Pin-Jun Wan; Qiang Fu (Insect Biochemistry and Molecular Biology, 2025)

Mitigating frost heave of a soil stabilized with sisal fiber exposed to freeze-thaw cycles - Fei Deng; Jianguo Lu; Xusheng Wan; Boshi Liu; Binlong Zhang; Hao Fu (Geotextiles and Geomembranes, 2025)

Reforestation practices have varied the resilience of nosZ-type denitrifier communities: A 40-year soil chronosequence study - Haoyan Xiao; Hanxia Yu; Juntao Wang; Lulu He; Zhenyu Wang; Yanrong Fu; Xiaohua Wan; Jason K. Reynolds; Zhiqun Huang (Applied Soil Ecology, 2025)

Profiling of chromatin accessibility and regulatory elements toward understanding the mechanisms underlying growth regulation in the Pacific oyster (Crassostrea gigas) - Ke Wan; Chenyu Shi; Yongjing Li; Liting Ren; Huiru Fu; Qi Li; Shikai Liu (Aquaculture, 2025)

Cynbungenins A-K, structurally diverse steroids with cytotoxic activity from the roots of Cynanchum bungei Decne - Xiao-San Li; Ming-Shang Liu; Wan-Bi Feng; Yu-Hao Luo; Wei-Bin Yuan; Ting-Ting Li; Xiao-Fu Peng; Yong-Mei Huang; Xue-Mei Yang; Hui Luo (Phytochemistry, 2025)

Low-temperature glucose foaming to construct three-dimensionally porous bulk CoMo catalyst for thiophene hydrodesulfurization - Yeqiang Du; Longzhou Ren; Wenjing Song; Ziqi Wan; Qinqin Zhang; Liancheng Bing; Fang Wang; Guangjian Wang; Haitao Fu; Dezhi Han (Fuel, 2025)

3,5-Dicaffeoylquinic acid promotes intestinal urate excretion via the MAPK signaling pathway based on Caco-2 Cell model - Jiajing Liao; Jin Qian; Lijuan Rao; Suqin Lin; Chen Wang; Linqian Xu; Bing Yuan; Jiayi Yuan; Yin Wan; Guiming Fu (Food Bioscience, 2025)

The obesity-related mutation gene on nonalcoholic fatty liver disease - Yen-Yu Chen; Chi-Sheng Chen; Jee-Fu Huang; Wen-Hsiu Su; Chia-Yang Li; Wei-Shiun Chen; En-Sheng Lin; Wan-Long Chuang; Ming-Lung Yu; Shu-Chi Wang (Human Genetics, 2025)

A domain-decomposition-based parallel approach for 3D geological modeling using radial basis functions interpolation on GPUs - Hong Li; Huizhu Ni; Jinming Fu; Bo Wan; Deping Chu; Fang Fang; Run Wang; Guoxi Ma; Xin Zhou (Earth Science Informatics, 2025)

Dietary Iron Overload Triggers Hepatic Metabolic Disorders and Inflammation in Laying Hen - Yue Li; Lan-Xin Li; Han Cui; Wan-Xue Xu; Hong-Yu Fu; Jiu-Zhi Li; Rui-Feng Fan (Biological Trace Element Research, 2025)

National investigation of bisphenols in the surface soil in China - Chang-Yu Weng; Ying-Ying Zhang; Fu-Jie Zhu; Shi-Ming Jia; Wan-Li Ma (Science of The Total Environment, 2024)

Highly efficient recovery of gold by thermally modified pyrite and its mechanism - Yuhong Fu; Can Wu; Qin Liu; Shanshan Li; Sen Li; Shuai Zhang; Quan Wan (Minerals Engineering, 2024)

Better waste utilization: Mg-modified biochar from wetland plant waste for phosphorus removal and carbon sequestration - Tingting Wang; Xinxi Fu; Yonghua Chen; Jingdong Wu; Yuanyuan Wang; Honghai Wan; Xiangyu Li; Lizhen Zhao (Journal of Environmental Chemical Engineering, 2024)

Transcriptomic reveals the effect of tannic acid stress on the cellular structure and growth of Saccharomyces cerevisiae - Yixin Huang; Mengfei Deng; Yanru Chen; Wenqin Cai; Na Liu; Yin Wan; Xiaodan Wu; Guiming Fu (Food Bioscience, 2024)

Associations between multiple metals exposure and cognitive function in the middle-aged and older adults from China: A cross-sectional study - Shiru Hong; Sheng Wu; Zhengce Wan; Chenming Wang; Xin Guan; Ming Fu; Chenliang Liu; Tianhao Wu; Guorong Zhong; Yuhan Zhou; Yang Xiao; Yingqian You; et al. (Environmental Research, 2024)

Bio-inspired sustainable electrospun quantum nanostructures for high quality factor enabled face masks and self-powered intelligent theranostics - Loganathan Veeramuthu; Ren-Jie Weng; Wei-Hung Chiang; Archana Pandiyan; Fu-Jie Liu; Fang-Cheng Liang; G. Ranjith Kumar; Hua-Yi Hsu; Yu-Ci Chen; Wen-Yinn Lin; Yao-Chun Tang; Wan-Rong Lin; et al. (Chemical Engineering Journal, 2024)

Toll-like receptor activation regulates the paracrine effect of adipose-derived mesenchymal stem cells on reversing osteoarthritic phenotype of chondrocytes - Zu Wan; Xin Wang; Zhenlan Fu; Yanming Ma; Gang Dai; Xiaoyuan Gong; Guangxing Chen; Liu Yang (Molecular Biology Reports, 2024)

Study on seasonal variations of Chaeturichthys stigmatias population resources and its environmental factors in marine ranching areas - Shike Gao; Yongqi Yao; Jinchi Wan; Shuo Zhang; Guanghui Fu; Jikun Lu (Ocean & Coastal Management, 2024)

Hydroxyapatite nanoparticle improves ovine oocyte developmental capacity by alleviating oxidative stress in response to vitrification stimuli - Qian Liu; Aiju Liu; Yucheng Liu; Jun Li; Jiachen Bai; Guiping Hai; Jingjing Wang; Weijun Liu; Pengcheng Wan; Xiangwei Fu (Theriogenology, 2024)

Rapid and extensive SARS-CoV-2 Omicron variant infection wave revealed by wastewater surveillance in Shenzhen following the lifting of a strict COVID-19 strategy - Yinghui Li; Chen Du; Ziquan Lv; Fuxiang Wang; Liping Zhou; Yuejing Peng; Wending Li; Yulin Fu; Jiangteng Song; Chunyan Jia; Xin Zhang; Mujun Liu; et al. (Science of The Total Environment, 2024)

Size-resolved gas-particle partitioning of polycyclic aromatic hydrocarbons in a large temperature range of 50 ℃ - De-Qi Wang; Shi-Ming Jia; Pu-Fei Yang; Fu-Jie Zhu; Wan-Li Ma (Journal of Hazardous Materials, 2024)

Effect of co-fermentation of non-Saccharomyces yeasts with Saccharomyces cerevisiae on the quality and flavor of blueberry wine - Xiaming Che; Bang Li; Jiali Zeng; Yanru Chen; Jingjing Liu; Wenwen Zeng; Wenqin Cai; Yin Wan; Guiming Fu (Food Research International, 2024)

Molecular characterization, spatio-temporal expression patterns of crtc2 gene and its immune roles in yellow catfish (Pelteobagrus fulvidraco) - Wan-Hong Zeng; Zheng-Yong Wen; Xiu-Ying Wei; Yu He; Luo Zhou; Peng Hu; Qing-Chao Shi; Chuan-Jie Qin; Jun Wang; Rui Li; Xiao-Ying Jing; Wei Hu; et al. (Fish & Shellfish Immunology, 2024)

Deformation prediction model of large-span prestressed structure for health monitoring based on robust Gaussian process regression - Wenwei Fu; Yi Chen; Yaozhi Luo; Hua-Ping Wan; Zhi Ma; Yanbin Shen (Engineering Structures, 2024)

A novel temperature-responsive biphasic deep eutectic solvent-based solvent system: Integrated efficient extraction, enrichment and recovery of phytochemicals - Zi-Hui Cai; Xin-Yue Dong; Li-Tao Wang; Wan-Mei Zhou; Ya-Ning Wang; Jie Yang; Yu-Jie Fu (Chemical Engineering Journal, 2024)

Improved forest height mapping using multibaseline low-frequency PolInSAR data based on effective selection of dual-baseline combinations - Yanzhou Xie; Haiqiang Fu; Jianjun Zhu; Changcheng Wang; Qinghua Xie; Jie Wan; Wentao Han (Remote Sensing of Environment, 2024)

Cytotoxic steroidal glycosides from Paris rugosa rhizomes - Jian-Ke Jia; Jun Yang; Xing-Zhi Yang; Ji-Feng Luo; Xiao-Yan Duan; Ying-Li Yang; Jin-Fu Wan; Yue-Hu Wang (Phytochemistry Letters, 2024)

Experimental study on the hydrodynamic of foldable-wing unmanned aerial-underwater vehicles during water-exit process - Zhaoliang Han; Jian Cao; Ye Li; Hongwei Li; Zipeng Du; Jinyu Fu; Lei Wan (Ocean Engineering, 2024)

New insight into bacterial communities of chicken manure composting under increased carbon to nitrogen ratios: Spatial heterogeneity in diversity, networks, and assembly processes - Xiaona Hu; Yangsen Jing; Nana Fu; Yongqi Wang; Dongsheng Qin; Xiaoying Guo; Yan Wang; Junfeng Wan (Journal of Environmental Chemical Engineering, 2024)

Positively charged loose nanofiltration membranes via the assembly of amino-quinone networks for efficient dye/salt separation - Tian Gao; Ping Fu; Wan-Long Li; Wan-Ting Lin; Yuan-Hui Yu; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Desalination, 2024)

A high-sensitivity and multi-response magnetic nanofiber-aerogel sensor with directionally aligned porous structure based on triple network for interactive human–machine interfaces - Yu Fu; Shuangkun Wang; Ye Tian; Boqiang Zhang; Zhihua Zhao; Zhenshuai Wan; Xingzhou Chen; Dengjie Zhu; Liuhua Yang; Zunghang Wei (Chemical Engineering Journal, 2024)

Nervonic acid and its sphingolipids: Biological functions and potential food applications - Nghi Van Phung; Fei Rong; Wan Yue Xia; Yong Fan; Xian Yu Li; Shi An Wang; Fu Li Li (Critical Reviews in Food Science and Nutrition, 2024)

Evaluation of the effect of Torulaspora delbrueckii on important volatile compounds in navel orange original brandy using E–nose combined with HS–SPME–GC–MS - Jingjing Liu; Yin Wan; Yanru Chen; Haowei Fan; Mengxiang Li; Qihai Jiang; Guiming Fu (Food Chemistry, 2024)

Transcriptomics to evaluate the influence mechanisms of ethanol on the ester production of Wickerhamomyces anomalus with the induction of lactic acid - Wenqin Cai; Yin Wan; Yanru Chen; Haowei Fan; Mengxiang Li; Shengwen Wu; Pei Lin; Tingting Zeng; Huibo Luo; Dan Huang; Guiming Fu (Food Microbiology, 2024)

Preparation of water-soluble dietary fiber from bamboo shoots by fungi fermentation and its supplementation in biscuits - Ying Shen; Ling Yang; Hong Peng; Limin Shen; Guiming Fu; Yin Wan; Yuhuan Liu; Xiaodan Wu; Hongli Zheng (Food and Bioproducts Processing, 2024)

Selenium alleviates pancreatic fibrosis in chickens caused by mercuric chloride: Involvement of the MAPK signaling pathway and selenoproteins - Yue Li; Han Cui; Dan Li; Hong-Yu Fu; Jiu-Zhi Li; Wan-Xue Xu; Rui-Feng Fan (Environmental Pollution, 2024)

Stable aryl-armed dihydrophenazines-based radicals - Lu Liu; Yuxuan Li; Haichang Fu; Xuecheng Guo; Qing Wan; Weijun Li; Ben Zhong Tang; Zhiming Wang (Chemical Engineering Journal, 2024)

The synthesis of papaya fruit flavor-related linalool was regulated by CpTPS18 and CpNAC56 - Yuan Yao; Wenhui Fu; Yue Yu; Suyan Wan; Wenping Zhang; Ray Ming (Plant Reproduction, 2024)

Cross-linked g-C3N4 nanofibers enable thermal stable composite membranes for high-performance loose nanofiltration - Wan-Ting Lin; Ping Fu; Wan-Long Li; Yuan-Hui Yu; Zi-Lu Zhang; Hong-Yu Fan; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Chemical Engineering Journal, 2024)

Modelling the dynamic gas/particle partitioning process of semi-volatile organic compounds emitted from point sources: Quantitative analysis and impact assessment - Fu-Jie Zhu; Li-Fu Wang; Long-Ze Qu; Wan-Li Ma; Geng-Bo Ren; Ben-Hang Li; Xiao-Dong Ma (Science of The Total Environment, 2024)

Pollution characteristics, source apportionment and absorption spectra of size-resolved PAHs in atmospheric particles in a cold megacity of China - De-Qi Wang; Shi-Ming Jia; Li-Yan Liu; Zi-Feng Zhang; Fu-Jie Zhu; Wan-Li Ma (Journal of Hazardous Materials, 2024)

Effects of freeze-thaw cycles on the quality of Hot-dry noodles: From the moisture, starch, and protein characteristics - Liuyu Wan; Xiude Wu; Peng Xu; Yaonan Xing; Shensheng Xiao; Yang Fu; Xuedong Wang (Food Chemistry, 2024)

Combined multi-omics approach to analyze the flavor characteristics and formation mechanism of gabaron green tea - Dongzhu Huang; Dongqiao Zheng; Chenyi Sun; Maoyin Fu; Yuhan Wu; Hong Wang; Jieyao Yu; Yunqiu Yang; Yeyun Li; Xiaochun Wan; Qi Chen (Food Chemistry, 2024)

Risk of heavy metal(loid) compositions in fine particulate matter on acute cardiovascular mortality: a poisson analysis in Anyang, China - Chaofan Shi; Jianjun Zhi; Hongsheng Zhao; Wan Wang; Hongjin Zhang; Guoyu Zhou; Xiaoli Fu; Yue Ba (International Journal of Biometeorology, 2024)

Divergent patterns of rainfall regimes in dry and humid areas of China - Ying Hu; Fangli Wei; Bojie Fu; Shuai Wang; Xiangming Xiao; Yuanwei Qin; Shihua Yin; Zhuangzhuang Wang; Lingfan Wan (Journal of Hydrology, 2024)

Enhancing the recovery of complex amino acids from excess sludge via low-intensity ultrasound-assisted enzymatic hydrolysis - Yixin Yan; Zhixuan Fu; Junfeng Wan; Yajing Zhang; Jianlei Gao; Jingqing Gao; Wei Wang (Chemical Engineering Journal, 2024)

Disruption of PABPN1 phase separation by SNRPD2 drives colorectal cancer cell proliferation and migration through promoting alternative polyadenylation of CTNNBIP1 - Zhijie Hu; Mengxia Li; Yufeng Chen; Liutao Chen; Yuting Han; Chengyong Chen; Xin Lu; Nan You; Yawen Lou; Yingye Huang; Zhanfeng Huo; Chao Liu; et al. (Science China Life Sciences, 2024)

Hemodialysis bilayer bionic blood vessels developed by the mechanical stimulation of hepatitis B viral X (HBX) gene-transfected hepatic stellate cells - Hongyi Liu; Yuanyuan Zhou; Peng Guo; Xiongwei Zheng; Weibin Chen; Shichao Zhang; Yu Fu; Xu Zhou; Zheng Wan; Bin Zhao; Yilin Zhao (Journal of Zhejiang University-SCIENCE B, 2024)

Identification of SNPs and candidate genes associated with growth using GWAS and transcriptome analysis in Coilia nasus - Yue Yu; Shi-Ming Wan; Shuang-Meng Zhang; Jun-Qi Liu; Ai-Li Sun; Yao Wang; Yong-Fu Zhu; Shu-Xin Gu; Ze-Xia Gao (Aquaculture, 2024)

Unlocking the power of activated carbon-mediated peracetic acid activation for efficient antibiotics abatement in groundwater: Coupling the processes of electron transfer, radical production, and adsorption - Si Li; Chaomeng Dai; Jixiang Li; Yanping Duan; Rongbing Fu; Yalei Zhang; Jiajun Hu; Lang Zhou; Luochao Wan; Qiming Zhang; Zhibo Zhang (Journal of Hazardous Materials, 2024)

Dominant contribution of combustion-related ammonium during haze pollution in Beijing - Libin Wu; Peng Wang; Qiang Zhang; Hong Ren; Zongbo Shi; Wei Hu; Jing Chen; Qiaorong Xie; Linjie Li; Siyao Yue; Lianfang Wei; Linlin Song; et al. (Science Bulletin, 2024)

Adsorption of antibiotics on microplastics (MPs) in aqueous environments: The impacts of aging and biofilms - Hongliang Ji; Siwen Wan; Zhenzhong Liu; Xianchuan Xie; Xiaofang Xiang; Lili Liao; Weikang Zheng; Zhengguo Fu; Peng Liao; Ronglong Chen (Journal of Environmental Chemical Engineering, 2024)

Integration of bulk-surface charge polarization and active site manipulation for highly efficient photocatalytic aerobic oxidation of sulfides - Jun Wan; Yang-Ai Ma; Yina Nie; Junhao Cheng; Chengming Wang; Lin Liu; Feng Fu (Chemical Engineering Journal, 2024)

Effects of Chemical Fixatives on Kinetic Measurements of Biomolecular Interaction on Cell Membrane - Tianbao Dong; Shengyang Wan; Yanhui Wang; Yaru Fu; Pengcheng Wang (The Journal of Membrane Biology, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Dynamic changes in butyrate levels regulate satellite cell homeostasis by preventing spontaneous activation during aging - Shujie Chen; Liujing Huang; Bingdong Liu; Huimin Duan; Ze Li; Yifan Liu; Hu Li; Xiang Fu; Jingchao Lin; Yinlan Xu; Li Liu; Dan Wan; et al. (Science China Life Sciences, 2024)

Study on the influence of spatial variability of soil strength parameters on reliability and slip surfaces of cofferdam slope reinforced by geosynthetic reinforcement - Yukuai Wan; Hongsong Fu; Yuke Wang (Marine Georesources & Geotechnology, 2024)

miR-15b-5p promotes HgCl2-induced chicken embryo kidney cells ferroptosis by targeting β-TrCP-mediated ATF4 ubiquitin degradation - Hong-Yu Fu; Yue Li; Han Cui; Jiu-Zhi Li; Wan-Xue Xu; Xi Wang; Rui-Feng Fan (Toxicology, 2024)

Effect of magnetic-spring bi-stable nonlinear energy sink on vibration and damage reduction of concrete double-column piers: Experimental and numerical analysis - Jundong Fu; Shui Wan; Peng Zhou; Jiwei Shen; Mia Loccufier; Kevin Dekemele (Engineering Structures, 2024)

Highly efficient solution-processable four-coordinate boron compound: A thermally activated delayed fluorescence emitter with short-lived phosphorescence for OLEDs with small efficiency roll-off - Zhengqin Pan; Jie Pan; Long Sang; Zhenming Ding; Meihua Liu; Laichao Fu; Mengqiu Wang; Xiaokang Huang; Bowen Li; Shaofeng Chen; Dongcheng Chen; Yu Liu; et al. (Chemical Engineering Journal, 2024)

Multi-crosslinked hydrogel built with hyaluronic acid-tyramine, thiolated glycol chitosan and copper-doped bioglass nanoparticles for expediting wound healing - Yifeng Yu; Congcong Wang; Qiaoqin Fu; Ying Wan; Aixi Yu (Carbohydrate Polymers, 2024)

Knockdown of SIK3 in the CA1 Region can Reduce Seizure Susceptibility in Mice by Inhibiting Decreases in GABAAR α1 Expression - Zhen-Fu Jiang; Li-Na Xuan; Xiao-Wan Sun; Shao-Bo Liu; Jian Yin (Molecular Neurobiology, 2024)

GDF15 as a key disease target and biomarker: linking chronic lung diseases and ageing - Yang Wan; Jianhua Fu (Molecular and Cellular Biochemistry, 2024)
Growth differentiation factor 15 (GDF15), a member of the transforming growth factor-beta superfamily, is expressed in several human organs. In particular, it is highly expressed in the placenta, prostate, and liver. The expression of GDF15 increases under cellular stress and pathological conditions. Although numerous transcription factors directly up-regulate the expression of GDF15, the receptors and downstream mediators of GDF15 signal transduction in most tissues have not yet been determined. Glial cell-derived neurotrophic factor family receptor α-like protein was recently identified as a specific receptor that plays a mediating role in anorexia. However, the specific receptors of GDF15 in other tissues and organs remain unclear. As a marker of cell stress, GDF15 appears to exert different effects under different pathological conditions. Cell senescence may be an important pathogenetic process and could be used to assess the progression of various lung diseases, including COVID-19. As a key member of the senescence-associated secretory phenotype protein repertoire, GDF15 seems to be associated with mitochondrial dysfunction, although the specific molecular mechanism linking GDF15 expression with ageing remains to be elucidated. Here, we focus on research progress linking GDF15 expression with the pathogenesis of various chronic lung diseases, including neonatal bronchopulmonary dysplasia, idiopathic pulmonary fibrosis, chronic obstructive pulmonary disease, and pulmonary hypertension, suggesting that GDF15 may be a key biomarker for diagnosis and prognosis. Thus, in this review, we aimed to provide new insights into the molecular biological mechanism and emerging clinical data associated with GDF15 in lung-related diseases, while highlighting promising research and clinical prospects.

Short-term effects of exposure to ambient PM2.5 and its components on hospital admissions for threatened and spontaneous abortions: A multicity case-crossover study in China - Heng He; Na Wan; Zhenzhen Li; Zihan Zhang; Zesen Gao; Qingdan Liu; Xiaolei Ma; Yuqing Zhang; Rongxiang Li; Xiuhong Fu; Weihong Qiu (Chemosphere, 2024)

Occurrence, seasonal variation and gas/particle partitioning of current used pesticides (CUPs) across 60 °C temperature and 30° latitudes in China - Liang Wang; Gang Cao; Zi-Feng Zhang; Li-Yan Liu; Shi-Ming Jia; Meng-Qi Fu; Wan-Li Ma (Journal of Hazardous Materials, 2024)

Topological analysis, endogenous mechanisms, and supply risk propagation in the polycrystalline silicon trade dependency network - Chaohao miao; Yanfang wan; Meiling kang; Fu Xiang (Journal of Cleaner Production, 2024)

Molar ratio of (-)-epicatechin and (-)-epigallocatechin gallate determined their enzymatic oxidation products and color characteristics - Li Lian; Yuqing Cui; Mingchun Wen; Daniel Granato; Yong-Quan Xu; Yan-Qing Fu; Zongde Jiang; Jiaping Ke; Xiaochun Wan; Liang Zhang (Food Bioscience, 2024)

Genetics and metabolic responses of Artemisia annua L to the lake of phosphorus under the sparingly soluble phosphorus fertilizer: evidence from transcriptomics analysis - Lingyun Wan; Juan Huo; Qiulan Huang; Xiaowen Ji; Lisha Song; Zhanjiang Zhang; Limei Pan; Jine Fu; Mohamed A. Abd Elhamid; Salma A. Soaud; Rania M. Y. Heakel; Jihai Gao; et al. (Functional & Integrative Genomics, 2024)

Luteolin inhibits the JAK/STAT pathway to alleviate auditory cell apoptosis of acquired sensorineural hearing loss based on network pharmacology, molecular docking, molecular dynamics simulation, and experiments in vitro - Fang Guo; Yingyuan Guo; Dejun Zhang; Zeming Fu; Shuang Han; Yining Wan; Guofang Guan (Toxicology and Applied Pharmacology, 2024)

Functional magnetic alginate/gelatin sponge-based flexible sensor with multi-mode response and discrimination detection properties for human motion monitoring - Yu Fu; Shuangkun Wang; Zhenshuai Wan; Ye Tian; Dong Wang; Yuelong Ma; Liuhua Yang; Zunghang Wei (Carbohydrate Polymers, 2024)

Research progress of anti-environmental factor stress mechanism and anti-stress tolerance way of Saccharomyces cerevisiae during the brewing process - Yanru Chen; Yili Yang; Wenqin Cai; Jiali Zeng; Na Liu; Yin Wan; Guiming Fu (Critical Reviews in Food Science and Nutrition, 2023)

Chronic cold environment regulates rheumatoid arthritis through modulation of gut microbiota-derived bile acids - Juan Liu; Fu Peng; Hao Cheng; Dandan Zhang; Yuxi Zhang; Lixia Wang; Fei Tang; Jing Wang; Yan Wan; Jing Wu; Yinlin Zhou; Wuwen Feng; et al. (Science of The Total Environment, 2023)

Cross-regional scale studies of organochlorine pesticides in air in China: Pollution characteristic, seasonal variation, and gas/particle partitioning - Liang Wang; Gang Cao; Li-Yan Liu; Zi-Feng Zhang; Shi-Ming Jia; Meng-Qi Fu; Wan-Li Ma (Science of The Total Environment, 2023)

Metabolomics and metatranscriptomics reveal the influence mechanism of endogenous microbe (Staphylococcus succinus) inoculation on the flavor of fermented chili pepper - Yumeng Li; Xiaoqin Luo; Huan Guo; Jinrong Bai; Yue Xiao; Yuan Fu; Yanping Wu; Hongyu Wan; Yina Huang; Hong Gao (International Journal of Food Microbiology, 2023)

Ultrasonic–microwave synergistic supramolecular solvent liquid–liquid microextraction of trace biogenic amines in fish and beer based on solidification of floating organic droplet - Furong Jin; Xinyue Yin; Yang Wan; Jiukai Zhang; Jindi Wang; Xiangbo Fu; Tianxin Fu; Buwei Liu; Yongshi Chen; Bo Tian; Zhibiao Feng (Food Chemistry, 2023)

Exploring the stress mechanism of tannic acid on Saccharomyces cerevisiae based on transcriptomics - Mengxiang Li; Mengfei Deng; Yanru Chen; Haowei Fan; Yixin Huang; Yunhong Huang; Yin Wan; Guiming Fu (Food Bioscience, 2023)

Transcriptomic and metabonomic to evaluate the effect mechanisms of the growth and aroma-producing of Pichia anomala under ethanol stress - Yanru Chen; Yin Wan; Wenqin Cai; Xiaming Che; Xuehui Sun; Hong Peng; Huibo Luo; Dan Huang; Guiming Fu (Food Bioscience, 2023)

Interfacial adsorption of gold nanoparticles on arsenian pyrite: New insights for the transport and deposition of gold nanoparticles - Xin Nie; Quan Wan; Michael F. Hochella; Suxing Luo; Meizhi Yang; Shanshan Li; Yuhong Fu; Ping Zeng; Zonghua Qin; Wenbin Yu (Chemical Geology, 2023)

Canagliflozin ameliorates high glucose-induced apoptosis in NRK-52E cells via inhibiting oxidative stress and activating AMPK/mTOR-mediated autophagy - Hong Liu; Weidong Chen; Sheng Wan; Ye Chen; Mengjing Fu; Zengsi Wang; Fei Xiong; Yanmin Zhang (Molecular Biology Reports, 2023)

Editorial Expression of Concern: Induction of Human Bone Marrow Mesenchymal Stem Cells Differentiation into Neural-Like Cells Using Cerebrospinal Fluid - Ying Ye; Yin-Ming Zeng; Mei-Rong Wan; Xian-Fu Lu (Cell Biochemistry and Biophysics, 2023)

CDKN2B-AS1 mediates proliferation and migration of vascular smooth muscle cells induced by insulin - Hao-jie Jin; Zi-heng Wu; Bao-fu Zhang; Jie Deng; Yin-dong Xu; Xin-yu Wang; Zheng-yang Song; Xin-wu Lu; Wan-tie Wang; Xiang-tao Zheng (Cell and Tissue Research, 2023)

The hepatoprotective effects of plant-based foods based on the “gut–liver axis”: a prospective review - Qiongdan Hu; Wan Liao; Zhen Zhang; Sanjun Shi; Shuguang Hou; Ningping Ji; Xinjie Zhang; Qian Zhang; Yangyang Liao; Linghui Li; Zongping Zhu; Yi Chen; et al. (Critical Reviews in Food Science and Nutrition, 2023)

Retrogradation inhibition of wheat starch with wheat oligopeptides - Liuyu Wan; Xuedong Wang; Hongyan Liu; Shensheng Xiao; Wenping Ding; Xiuyun Pan; Yang Fu (Food Chemistry, 2023)

A novel oleogel based on porous microgel from egg white - Buwei Liu; Lina Sun; Furong Jin; Yang Wan; Xiue Han; Tianxin Fu; Yongjia Guan; Zhixin Xie; Long Cheng; Bo Tian; Zhibiao Feng (Food Hydrocolloids, 2023)

Laccase-triggered one-step fabrication of positively charged phenolic acid-amine networks for nanofiltration - Ping Fu; Di Zhou; Wan-Long Li; Wan-Ting Lin; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Desalination, 2023)

Efficient genome editing in cotton using the virus-mediated CRISPR/Cas9 and grafting system - Wei-Feng Guo; Dan-Dan Guo; Fen Li; Shen-Zhai Shang; Ting-Wan Li; Ying-Chao Tang; Man Jiang; Fu-Chun Xu; Wei Gao (Plant Cell Reports, 2023)

Individual and combined effects of herbicide prometryn and nitrate enrichment at environmentally relevant concentrations on photosynthesis, oxidative stress, and endosymbiont community diversity of coral Acropora hyacinthus - Qiuli Li; Dinghui Fu; Yanyu Zhou; Yuanchao Li; Liang Chen; Zhaofan Wang; Yinglang Wan; Zanhui Huang; Hongwei Zhao (Chemosphere, 2023)

Illustration on phenotypic and genotypic characteristics of typical multi-antibiotic resistant bacteria in aquatic environments through complete genomes and comparative genomics - Chunli Wan; Rui Tang; Liyan Deng; Liya Fu; Panxin Wang; Xiang Liu; Changyong Wu (Chemosphere, 2023)

Topology optimization on the attenuation degree of evanescent waves in periodic pile barriers - Xiao Wang; Shui Wan; Peng Zhou; Jundong Fu; Shuli Li (Soil Dynamics and Earthquake Engineering, 2023)

Emergence and ecological transition of the Mesozoic marine reptiles: Evidence from the Early Triassic Chaohu and the Middle Triassic Xingyi Faunas - Da-yong Jiang; Min Zhou; Ryosuke Motani; Andrea Tintori; Nicholas C. Fraser; Jian-dong Huang; Olivier Rieppel; Cheng Ji; Wan-lu Fu; Zuo-yu Sun; Hao Lu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Insights on the binding mechanism between specified aldehydes and flaxseed protein using multispectral image and molecular docking - Lingxia Xu; Yilai Wan; Xiaoxiao Liu; Zhaoyang Qin; Yue Zhao; Xizhe Fu; Changqing Wei; Wenyu Liu (Food Chemistry, 2023)

Transcriptional analysis reveals formation of axillary solitary hook in vine plant Uncaria rhynchophylla - Lingyun Wan; Limei Pan; Lisha Song; Jine Fu; Qiulan Huang; Xiaowen Ji; Shugen Wei; Zhanjiang Zhang (Plant Biotechnology Reports, 2023)
The hook of Uncaria rhynchophylla is an important external phenotype representing the quality of Gou-Teng. The hook formation pattern of U. rhynchophylla displays a unique feature that solitary hook and opposite hooks alternately occur in the leaf axils forming a liner series. The solitary hook only grows on the lower side of the leaf axil, resulting from the decline in the total yield of hooks. However, the reasons for solitary hook formation in U. rhynchophylla are not clear. Therefore, a survey on the molecular mechanisms of solitary hook formation needs to be performed urgently. We obtained 250.67 million high-quality clean reads from the lower side of axillary stem segments (HS) and the upper side of axillary stem segments (HSCK) libraries. We detected 42 DEGs (differentially expressed genes) between HS and HSCK libraries; 11 were down-regulated, and 31 were up-regulated. Gene ontology functional classification of the DEGs indicated that they included two genes that encoded LAZY1 related to the regulation of polar auxin transport, two genes that encoded AUX/IAA and AP2/ERF related to plant hormone signaling transduction, and two genes that encoded F3H related to the flavone synthase activity. These six genes were associated with lateral polar auxin transport (PAT) regulation, and their expression level had a high correlation with the pattern of IAA distribution upon gravity stimulation. And the inhibition of solitary hook development was observed after treatment with N -1-naphthylphthalamic acid (NPA) or quercetin, which was known as the polar auxin inhibitor. The above findings might provide new information about the molecular mechanisms of regulation of lateral PAT in the axillary bud development process under gravity.

A Semantic Network Method for the Identification of Ship’s Illegal Behaviors Using Knowledge Graphs: A Case Study on Fake Ship License Plates - Hui Wan; Shanshan Fu; Mingyang Zhang; Yingjie Xiao (Journal of Marine Science and Engineering, 2023)
With the advancement of intelligent shipping, current traffic management systems have become inadequate to meet the requirements of intelligent supervision. In particular, with regard to ship violations, on-site boarding is still necessary for inspection. This paper presents a novel approach for enhancing ships’ management and service capabilities through scientific knowledge graph technology to develop a ship knowledge graph. The proposed approach extracts key characteristics of ship violations from the ship knowledge graph, such as monitoring ships, expired ship certificates, multiple ship tracks, inconsistent ship tracks with port reports, and ships not reported to the port for a long time. Combining the characteristics of ship violations, the approach uses reasoning and identification techniques to detect specific instances of falsely licensed ships and other violations. The development of the ship knowledge graph analysis system enables the identification and verification of illegal ships using fake license plates, while also improving the effective utilization of maritime data and enhancing the ability to make informed decisions related to ship safety. By leveraging cognitive approaches and knowledge graphs, this study offers the potential to develop an intelligent decision-making system for maritime traffic management.

Molecular characterization, spatiotemporal expression patterns of fatty acid elongase (elovl8) gene, and its transcription changes in response to different diet stimuli in yellow catfish (Pelteobagrus fulvidraco) - Wan-Hong Zeng; Xiu-Ying Wei; Wei Qin; Chuan-Jie Qin; Qiong Shi; Sheng-Tao Guo; Panita Prathomya; Shi-Yong Zhang; Peng Fu; Wei Hu; Han-Wen Yuan; Zheng-Yong Wen (Frontiers in Marine Science, 2023)
Elongase of very long-chain fatty acid 8 (Elovl8) is a new member identified in the Elovl family that is involved in the synthesis of highly unsaturated fatty acids (HUFAs). However, the evolutionary and physiological roles of this enzyme are still largely unknown. In the present study, the elovl8 gene was identified and characterized from yellow catfish Pelteobagrus fulvidraco , and then its evolutionary and molecular characteristics as well as transcriptional changes in response to various nutritional status were determined. Results showed that the open reading frame (ORF) of elovl8 was 795 bp in length, encoding a protein of 264 amino acids. Multiple sequences alignment showed that the yellow catfish Elovl8 was highly conserved with other homologs in teleosts, sharing similar structural characteristics (including six conserved transmembrane α-helical domains, four conserved elongase motifs, and three highly conserved cysteine residues). Meanwhile, comparisons of genetic synteny confirmed that the elovl8 gene identified from the yellow catfish was the homolog of elovl8b in other teleosts, and thus, the elovl8a gene was lost in the genome of the yellow catfish. Gene structure analysis revealed that the elovl8b gene contained eight exons and seven introns, which was highly conserved in teleosts, implying the functional conservation among various fish species. Tissue distribution analysis detected by real-time quantitative PCR (RT-qPCR) showed that the elovl8 gene was extensively expressed in all detected tissues except eyes, with high expression levels in the intestine and liver. Temporal expression analysis revealed that the expression level of elovl8 was stably expressed in the early 12 h after fertilization, and then dramatically decreased at 24, 48, 72, and 96 h after fertilization, implying that elovl8 is required for HUFA biosynthesis in the early development stages. Functional experiments showed that the expression of the elovl8 gene was stimulated after feeding with egg yolk but was not obviously affected after feeding with halogenated worms, indicating that diets full of HUFAs can inhibit the expression of elovl8 in yellow catfish. Our findings will help us to better understand the evolutionary and functional characteristics of elovl8 in teleosts, and lay a solid basis for investigating the regulation mechanism of HUFA biosynthesis.

TIPS: A three-dimensional phenotypic measurement system for individual maize tassel based on TreeQSM - Bo Xu; Xiangyuan Wan; Hao Yang; Haikuan Feng; Yuanyuan Fu; Haiyan Cen; Binbin Wang; Zhoufeng Zhang; Siyuan Li; Chunjiang Zhao; Guijun Yang (Computers and Electronics in Agriculture, 2023)

Characteristics of persulfate gel materials in groundwater remediation: Column and tank experiments investigations - Yu Yang; Xiangjian Xu; Fu Xia; Shuoyang Wan; Xu Han; Han Xiao; Sheng Deng; Yonghai Jiang; Xiang Li (Science of The Total Environment, 2023)

Diagnostic REE patterns of magmatic and hydrothermal apatite in the Zhuxi tungsten skarn deposit, China - Xia-Nan Zhang; Jia-Yong Pan; Bernd Lehmann; Jin-Xiang Li; Shuo Yin; Yong-Peng Ouyang; Bin Wu; Jia-Li Fu; Yong Zhang; Yue Sun; Jian-Jun Wan; Tong Liu (Journal of Geochemical Exploration, 2023)

Local provincialism of late Permian plant–arthropod associations in South Cathaysia: Evidence of arthropod-mediated damages in a Wuchiapingian assemblage of South China - Fu-Jun Ma; Die-Die Luo; Song Liu; Cheng-Wan Zhang; Qiu-Jun Wang; Bing-Xia Li; Chuan-Yuan Liu; Bai-Nian Sun; Xiao He (Journal of Asian Earth Sciences, 2023)

mTORC1/rpS6 and mTORC2/PKC regulate spermatogenesis through Arp3-mediated actin microfilament organization in Eriocheir sinensis - Zhen-Fang Li; Hong-Yu Qi; Jia-Ming Wang; Zhan Zhao; Fu-Qing Tan; Wan-Xi Yang (Cell and Tissue Research, 2023)

A novel electrochemical aptasensor based on eco-friendly synthesized titanium dioxide nanosheets and polyethyleneimine grafted reduced graphene oxide for ultrasensitive and selective detection of ciprofloxacin - Yangguang Zhu; Xiufen Li; Mengfan Wu; Mingjiao Shi; Qichen Tian; Li Fu; Hsu-Sheng Tsai; Wan-Feng Xie; Guosong Lai; Gang Wang; Nan Jiang; Chen Ye; et al. (Analytica Chimica Acta, 2023)

Interaction of silver nanoparticles with marine/lake snow in early formation stage - Jing Wan; Juefei Ye; Yibo Zhang; Zhang Li; Zhenbing Wu; Chenyuan Dang; Jie Fu (Water Research, 2023)

Exposure to ZnO nanoparticles induced blood-milk barrier dysfunction by disrupting tight junctions and cell injury - Jingjing Wang; Mingzhen Jiang; Guangchao Wan; Yiwu Fu; Yingrong Ye; Hanpeng Wu; Yichun Chen; Yao Chen; Youpeng Sun; Xia Wang; Ershun Zhou; Zhengtao Yang (Toxicology Letters, 2023)

Dihydromyricetin attenuates cisplatin-induced acute kidney injury by reducing oxidative stress, inflammation and ferroptosis - Zheming Xu; Minjing Zhang; Wenwen Wang; Suhan Zhou; Minghua Yu; Xingyu Qiu; Shan Jiang; Xiaohua Wang; Chun Tang; Shuijie Li; Chih-Hong Wang; Runzhi Zhu; et al. (Toxicology and Applied Pharmacology, 2023)

Vibration mitigation in porous soil using periodic rock-socketed pile barriers - Xiao Wang; Shui Wan; Peng Zhou; Jundong Fu; Zhiqiang Wu (Soil Dynamics and Earthquake Engineering, 2023)

Organic aerosols in the inland Tibetan Plateau: New insights from molecular tracers - Xin Wan; Pingqing Fu; Shichang Kang; Kimitaka Kawamura; Guangming Wu; Quanlian Li; Shaopeng Gao; Zhiyuan Cong (Science of The Total Environment, 2023)

ZmMS1/ZmLBD30-orchestrated transcriptional regulatory networks precisely control pollen exine development - Quancan Hou; Xueli An; Biao Ma; Suowei Wu; Xun Wei; Tingwei Yan; Yan Zhou; Taotao Zhu; Ke Xie; Danfeng Zhang; Ziwen Li; Lina Zhao; et al. (Molecular Plant, 2023)

Effectively removing gaseous polycyclic aromatic hydrocarbons (PAHs) by willow catkins: Do you still dislike the catkins floating? - Peng-Tuan Hu; Dong-Hai Liu; Zhi-Guo Cao; Hong Wei; Fu-Jie Zhu; Wan-Li Ma; Zi-Feng Zhang; Li-Yan Liu; Jing-Lan Feng; Yong-Feng Li; Yu-Fei Li; Yi-Fan Li (Journal of Hazardous Materials, 2023)

TiO2 nanoparticles affect spermatogenesis and adhesion junctions via the ROS-mediated mTOR signalling pathway in Eriocheir sinensis testes - Lan-Min Wang; Ke Jia; Zhen-Fang Li; Hong-Yu Qi; Ding-Xi Liu; Ya-Jing Liang; Shuang-Li Hao; Fu-Qing Tan; Wan-Xi Yang (Environmental Pollution, 2023)

Health Risk Assessment of Organophosphate Flame Retardants in Soil Across China Based on Monte Carlo Simulation - Mei-Hong Chen; Shi-Ming Jia; Pu-Fei Yang; Fu-Jie Zhu; Wan-Li Ma (Archives of Environmental Contamination and Toxicology, 2023)

Anti-inflammatory lanostane triterpenoids with rearranged spirobi[indene] scaffold and their biogenetically related analogues from Euphorbia maculata - Ru-Feng Xia; Jun-Cheng Su; Jun Yu; Hong-Jing Zha; Jia-Le Wu; Xiao-Na Fu; Qin Cai; Luo-Sheng Wan (Phytochemistry, 2023)

A new configuration of Geiger-type cable domes with sliding ridge cables: Computational framework and structural feasibility investigation - Yu Xue; Yaozhi Luo; Yafeng Wang; Xian Xu; Hua-Ping Wan; Yanbin Shen; Wenwei Fu (Engineering Structures, 2023)

Retraction Note: Two New Coordination Polymers: Selective Detection of Cu(II) Ion and Treatment Activity on Inner Ear Damage - Jing Liu; Wan-Dong She; Fu-Sen Wang; Qing Zhou (Journal of Fluorescence, 2023)

Influence on the levels of PAHs and methylated PAHs in surface soil from pollution control in China: Evidence in 2019 data compared with 2005 and 2012 data - Fu-Jie Zhu; Zi-Feng Zhang; Li-Yan Liu; Hong Yao; Hong-Liang Jia; Zhi Zhang; Song Cui; Bo Meng; Gang Cao; Peng-Hao Su; Xiao-Xuan Mao; Bao-Long Li; et al. (Science of The Total Environment, 2023)

Two generations of crustal anatexis in association with two-stage exhumation of ultrahigh-pressure metamorphic rocks in the Dabie orogen - Qiong-Xia Xia; Meng Yu; Er-Lin Zhu; Ren-Xu Chen; Wan-Cai Li; Yong-Fei Zheng; Zi-Fu Zhao; Zhao-Ya Li (Lithos, 2023)

Is the petrochemical industry an overlooked critical source of environmental microplastics? - Liyan Deng; Hongbo Xi; Chunli Wan; Liya Fu; Yue Wang; Changyong Wu (Journal of Hazardous Materials, 2023)

Brief report prevalence of Echinococcus species in wild foxes in parts of Qinghai Province, China - Xueyong Zhang; Yong Fu; Yijuan Ma; Zhihong Guo; Xiuying Shen; Zhi Li; Gengqiu Jiunai; Xiaohong Wang; Wan Maji; Hong Duo (Veterinary Research Communications, 2023)

RNA sequencing in Artemisia annua L explored the genetic and metabolic responses to hardly soluble aluminum phosphate treatment - Lingyun Wan; Qiulan Huang; Xiaowen Ji; Lisha Song; Zhanjiang Zhang; Limei Pan; Jine Fu; Rania G. Elbaiomy; Ahmed S. Eldomiaty; Shabir A. Rather; Mohamed M. A. Elashtokhy; Jihai Gao; et al. (Functional & Integrative Genomics, 2023)

Causes of the discordance in the south-north distribution of the 2017 Jiuzhaigou earthquake sequences - Zhi-Tong Jin; Jia-Lu Liu; Yong-Ge Wan; Shu-Zhong Sheng; Fu-Chang Wang; Xiao-Tao Zhang; Gan Feng (Applied Geophysics, 2023)

Solid-phase extraction and separation of indium with P2O4-UiO-66-MOFs (di-2-ethylhexyl phosphoric acid-UiO-66-metal-organic frameworks) - Wan-Yi Zeng; Minzhong Huang; Minglai Fu (Journal of Environmental Sciences, 2023)

Comparison of methods for detecting protein extracted from excess activated sludge - Yixin Yan; Mengnan Zhang; Jianlei Gao; Lei Qin; Xi Fu; Junfeng Wan (Environmental Science and Pollution Research, 2023)

Regulating the reaction pathway of nZVI to improve the decontamination performance through magnetic spatial confinement effect - Hai-Yuan Chi; Xiao-Xia Zhou; Min-Rong Wu; Wan-yu Shan; Jing-fu Liu; Jin-quan Wan; Bing Yan; Rui Liu (Journal of Hazardous Materials, 2023)

Changes in the physicochemical and protein distribution properties of dough with the wheat oligopeptide incorporation - Hongyan Liu; Liuyu Wan; Shensheng Xiao; Yang Fu; Xuedong Wang (Food Bioscience, 2023)

Prediction of column failure modes based on artificial neural network - Haitao Wan; Yongle Qi; Tiejun Zhao; Wenjuan Ren; Xiaoyan Fu (Earthquake Engineering and Engineering Vibration, 2023)

Non-target scanning of organics from cooking emissions using comprehensive two-dimensional gas chromatography-mass spectrometer (GC×GC-MS) - Kai Song; Song Guo; Yuanzheng Gong; Daqi Lv; Zichao Wan; Yuan Zhang; Zihao Fu; Kun Hu; Sihua Lu (Applied Geochemistry, 2023)

Depth profiling of arsenian pyrite in Carlin-type ores through wet chemistry - Meizhi Yang; Quan Wan; Xin Nie; Suxing Luo; Yuhong Fu; Ping Zeng; Wenqi Luo (Acta Geochimica, 2023)

Deep kimberlite prospecting and thrust-nappe structure: Analysis of diamond metallogenic belt in Wafangdian, China - Mishan Zhong; Guoren Zhang; Haitao Fu; Haipeng Wang; Zhenghong Liu; Jin Liu; ZiJie Wu; Fuliang Gao; Yongzhao Gao; Yuqi Pan; Fanglai Wan; Lei Yang; et al. (International Geology Review, 2023)

Fabrication of casein-crocin nanocomplexes: Interaction mechanism, impact on stability and bioavailability of crocin - Haowei Fan; Guiming Fu; Silin Feng; Xinchao He; Wenqin Cai; Yin Wan (Food Hydrocolloids, 2023)

Denitrification efficiency, microbial communities and metabolic mechanisms of corn cob hydrolysate as denitrifying carbon source - Yingping Long; Yongwen Ma; Jinquan Wan; Yan Wang; Min Tang; Hao Fu; Jianye Cao (Environmental Research, 2023)

Laboratory-scale investigation of the material distribution characteristics of landslide dams in U-shaped valleys - Fu-xian Jian; Zheng-yin Cai; Wan-li Guo (Journal of Mountain Science, 2023)

Rhizosphere activity induced mobilization of heavy metals immobilized by combined amendments in a typical lead/zinc smelter-contaminated soil - Youfa Luo; Chuanjing Tan; Yu He; Yulu Chen; Zuyan Wan; Tianling Fu; Yonggui Wu (Chemosphere, 2023)

Enhanced production of sugars and UV-shielded lignin/PAN fiber mats from chemi-mechanical pulps - Lei Wang; Xiaohan Li; Chenzhong Wan; Kesheng Zhang; Zhao Wu; Fen Hu; Ran Zhang; Xiao Fu; Hongbo Yu (Science of The Total Environment, 2023)

National-scale monitoring of historic used organochlorine pesticides (OCPs) and current used pesticides (CUPs) in Chinese surface soil: Old topic and new story - Liang Wang; Zi-Feng Zhang; Li-Yan Liu; Fu-Jie Zhu; Wan-Li Ma (Journal of Hazardous Materials, 2023)

A review on lignin waste valorization by catalytic pyrolysis: Catalyst, reaction system, and industrial symbiosis mode - Shaoqing Wang; Zhen Wan; Yu Han; Yan Jiao; Zhihe Li; Peng Fu; Ning Li; Andong Zhang; Weiming Yi (Journal of Environmental Chemical Engineering, 2023)

A thermos-inspired double structural design for efficient and sustainable solar-driven water purification - Xinxian Li; Xinxi Fu; Yonghua Chen; Honghai Wan; Yuanyuan Wang; Hao Wang; Lingying Chen (Journal of Environmental Chemical Engineering, 2023)

Effects of temperature on the pharmacokinetics, optimal dosage, tissue residue, and withdrawal time of florfenicol in asian seabass ( lates calcarifer ) - Tirawat Rairat; Ming-Kun Hsieh; Wan-Cih Ho; Yi-Ping Lu; Zhu-Ying Fu; Niti Chuchird; Chi-Chung Chou (Food Additives & Contaminants: Part A, 2023)

Hormonal Profiling of Encapsulated and Nonencapsulated Rhizomes of Chinese Cymbidium in Different Storage Environments - Shuangbin Fu; Zhuang Zhou; Yanping Yang; Zhen Ying; Wan Xu (Journal of Plant Growth Regulation, 2023)

Water microecology is affected by seasons but not sediments: A spatiotemporal dynamics survey of bacterial community composition in Lake Changshou—The largest artificial lake in southwest China - Ai-ling Chen; Fu-qing Xu; Xia Su; Fu-pan Zhang; Wan-chao Tian; Shang-jie Chen; Fang Gou; Zhi-lin Xing; Jin-xin Xiang; Juan Li; Tian-tao Zhao (Marine Pollution Bulletin, 2023)

Organic matter accumulation mechanism under global/regional warming: Insight from the Late Barremian calcareous shales in the Qiangtang Basin (Tibet) - Ying Nie; Xiugen Fu; Xianchuan Liu; Hengye Wei; Shengqiang Zeng; Fei Lin; Youli Wan; Chunyan Song (Journal of Asian Earth Sciences, 2023)

Study on the quality characteristics of hot-dry noodles by microbial polysaccharides - Yixuan Liu; Xiaorong Liu; Liuyu Wan; Peng Xu; Xiaoyi Deng; Beibei Ding; Xuedong Wang; Yang Fu (Food Research International, 2023)

Poly(caffeic acid) as interlayer to enhance nanofiltration performance of polyamide composite membrane - Xiao-lei Wang; Ya-xian Xue; Shu-qian Dong; Qi Wang; Jiang-tao Yu; Hui-cai Wang; Huan Zhang; Wan Wang; Jun-fu Wei (Desalination, 2023)

Robust emission in near-infrared II of lanthanide nanoprobes conjugated with Au (LNPs-Au) for temperature sensing and controlled photothermal therapy - Guofeng Liu; Zhenxing Wang; Wan Sun; Xiaohui Lin; Rui Wang; Chonghui Li; Li Zong; Zuoling Fu; Hanping Liu; Shicai Xu (Chemical Engineering Journal, 2023)

Dual-site oxygen activation for enhanced photocatalytic aerobic oxidation by S-scheme Ni2P/Bi3O4Br-OVs heterojunction - Weijie Yang; Kailong Sun; Jun Wan; Yang-Ai Ma; Yu Wang; Lin Liu; Bicheng Zhu; Feng Fu (Chemical Engineering Journal, 2023)

Characteristics and evaluation of coastal erosion vulnerability of typical coast on Hainan Island - GuoWei Fu; Chao Cao; KaiZhe Fu; YanWei Song; Kun Yuan; XiaoMing Wan; ZiAng Zhu; ZhaoFan Wang; ZanHui Huang (Frontiers in Marine Science, 2022)
Coastal erosion vulnerability assessment is widely used to assess the loss degree of coastal zone caused by erosion, and plays an important role in coastal natural resources protection, planning, management and decision-making. Based on the natural and social characteristics of the east coast of Qiongdong and the coastal erosion vulnerability index (CVI) method, this study selected 8 assessment indicators, such as shoreline change rate (U1). The Delphi method and the entropy weight method were used to calculate the comprehensive index weight, combined with CVI method and geographic information system (GIS) technology, to quantitatively evaluate the temporal and spatial distribution characteristics of typical coastal erosion vulnerability such as coral reefs in the east of Hainan Island. The study area was divided into 5 grades: very low (31%), low (10%), moderate (28%), high (24%) and high vulnerability (7%), and the overall performance was moderate erosion vulnerability. The research showed that the interannual downward rate erosion of beach (U3) and the rate of change of the isobath (U2) of the beach were the main controlling factors affecting the vulnerability of coastal erosion in the study area, and the coastal dynamic factor had a greater impact than the other two factors. As a natural barrier, the coral reefs in the study area had good wave absorption and energy reduction, and the coral reef coasts showed low coastal erosion vulnerability, due to the complex hydrodynamic characteristics, estuary coasts is the most vulnerable areas. The verification results of the ROC-AUC method showed that the accuracy of erosion vulnerability was 68.9%, which provided an important reference for the ecological restoration of tropical coral reef biological coasts and the development and management of the Hainan Qiongdong coastal zone.

BCI system with lower-limb robot improves rehabilitation in spinal cord injury patients through short-term training: a pilot study - Zhengzhe Cui; Yongqiang Li; Sisi Huang; Xixi Wu; Xiangxiang Fu; Fei Liu; Xiaojiao Wan; Xue Wang; Yuting Zhang; Huaide Qiu; Fang Chen; Peijin Yang; et al. (Cognitive Neurodynamics, 2022)

Synthesis of Lanthanum-Modified Attapulgite and Its Phosphorus-Fixing Mechanism for Urban Eutrophic Lake - Lingfeng Ye; Ye Li; Cong Liu; Bolin Li; Dongxue Liu; Chang Liu; Jie Wan; Chengbin Fu (Water, Air, & Soil Pollution, 2022)

mTORC1/C2 regulate spermatogenesis in Eriocheir sinensis via alterations in the actin filament network and cell junctions - Zhen-Fang Li; Shuang-Li Hao; Lan-Min Wang; Hong-Yu Qi; Jia-Ming Wang; Fu-Qing Tan; Wan-Xi Yang (Cell and Tissue Research, 2022)

Distribution of ultrafine aerosols and volatile organic compounds from surgical smoke during electrocauterization - Chi-Tsung Chen; Shiang-Fu Huang; Cheng-Jung Li; Jou-Mien Huang; Kai-Ping Chang; Gwo-Hwa Wan (Air Quality, Atmosphere & Health, 2022)

Improving pre-harvest sprouting resistance in rice by editing OsABA8ox using CRISPR/Cas9 - Kai Fu; Weihan Song; Cheng Chen; Changling Mou; Yunshuai Huang; Fulin Zhang; Qixian Hao; Ping Wang; Tengfei Ma; Yaping Chen; Ziyan Zhu; Min Zhang; et al. (Plant Cell Reports, 2022)

Plasma Matrix Metalloproeteinase-9 Is Associated with Seizure and Angioarchitecture Changes in Brain Arteriovenous Malformations - Yo-Tsen Liu; Cheng-Chia Lee; Chun-Fu Lin; Hsiu-Mei Wu; Wan-Yuo Guo; Huai-Che Yang; Feng-Chi Chang; Kang-Du Liou; Chung-Jung Lin (Molecular Neurobiology, 2022)

Recent advances in alleviating food allergenicity through fermentation - Xiaowen Pi; Yili Yang; Yuxue Sun; Qiang Cui; Yin Wan; Guiming Fu; Hongbing Chen; Jianjun Cheng (Critical Reviews in Food Science and Nutrition, 2022)

Catalytic effect of cesium on the oxidation behavior of cation exchange resins in Li2CO3-Na2CO3-K2CO3 melt - Yang-Hai Zheng; Yong-De Yan; Yun Xue; Yue-Lin Wang; Xin Liu; Wan-Sheng Mi; Qing-Guo Zhang; Yu Li; Fu-Qiu Ma; Mi-Lin Zhang; Zhi-Hao Gan; Kai Zhu (Environmental Science and Pollution Research, 2022)

Food irradiation: a promising technology to produce hypoallergenic food with high quality - Xiaowen Pi; Yili Yang; Yuxue Sun; Xibo Wang; Yin Wan; Guiming Fu; Xin Li; Jianjun Cheng (Critical Reviews in Food Science and Nutrition, 2022)

Mapping Cell Phenomics with Multiparametric Flow Cytometry Assays - Yang Liu; Haichu Zhao; Boqiang Fu; Shan Jiang; Jing Wang; Ying Wan (Phenomics, 2022)
Phenomics explores the complex interactions among genes, epigenetics, symbiotic microorganisms, diet, and environmental exposure based on the physical, chemical, and biological characteristics of individuals and groups. Increasingly efficient and comprehensive phenotyping techniques have been integrated into modern phenomics-related research. Multicolor flow cytometry technology provides more measurement parameters than conventional flow cytometry. Based on detailed descriptions of cell phenotypes, rare cell populations and cell subsets can be distinguished, new cell phenotypes can be discovered, and cell apoptosis characteristics can be detected, which will expand the potential of cell phenomics research. Based on the enhancements in multicolor flow cytometry hardware, software, reagents, and method design, the present review summarizes the recent advances and applications of multicolor flow cytometry in cell phenomics, illuminating the potential of applying phenomics in future studies.

The safety degree evaluation of marine biodiversity in China - Xiu-Mei Fu; Wan-Yu Wu; Fang Yang; Shan-Shan Jiang; Shi-Qi Wang; Xiao-Yan Li; Hui-Ying Tang; Ying Liu; Chang-Yun Wang (Journal of Coastal Conservation, 2022)

Optimizing Hard Clam Production in Taiwan by Accounting for Nonlinear Effects of Stocking Density and Feed Costs on Farm Output of Clams - Jie-Min Lee; Sheng-Hung Chen; Yi-Chung Lee; Jung-Fu Huang; Christian Schafferer; Chun-Yuan Yeh; Ti-Wan Kung (Fishes, 2022)
Despite mass mortality, hard clams remain among the main cultured shellfish in Taiwan. Using cross-sectional data, this study applies threshold regression modeling with stocking density and feed costs as the threshold variables to explore the nonlinear relationship between input and output factors. The findings show that the production output levels may be increased by different combinations of factor inputs and variations in input factors. More specifically, the higher output levels may be achieved by increasing labor input while reducing capital input factors in farming households with a higher stocking density (HSD > 1,087,870 inds/ha) or higher feed cost (HFC > 13,889 NTD/ha). Farming households with a lower stocking density (LSD ≤ 1,087,870 inds/ha) may enhance production output levels by increasing feed input while reducing capital inputs. Moreover, the maximum output level of HSD and HFC farming households was estimated to reach 9255 kg/ha and 9807 kg/ha, respectively. Results of the production output simulation suggest that the feeding cost per hectare in LSD households should not exceed 25,119 NTD to avoid overfeeding, which may cause culture deterioration and lower survival rates. As such, farmers are advised to adjust their feed costs according to the stocking density to maximize production output.

Oral Enrichment of Streptococcus and its Role in Systemic Inflammation Related to Monocyte Activation in Humans with Cocaine Use Disorder - Xiaoyu Fu; Da Cheng; Zhenwu Luo; Amanda Wagner; Sylvia Fitting; Xiaomei Cong; Wanli Xu; Kendra Maas; Zhuang Wan; Jian Zhu; Zejun Zhou; William W. Stoops; et al. (Journal of Neuroimmune Pharmacology, 2022)

Chromosomes polymorphisms of Sichuan wheat cultivars displayed by ND-FISH landmarks - Zhenglei Hu; Jiangtao Luo; Linrong Wan; Jie Luo; Yazhou Li; Shulan Fu; Dengcai Liu; Ming Hao; Zongxiang Tang (Cereal Research Communications, 2022)

Risk assessment and support design optimization of a high slope in an open pit mine using the jointed finite element method and discontinuous deformation analysis - Jingyu Kang; Daochun Wan; Qian Sheng; Xiaodong Fu; Xin Pang; Luqing Xia; De Li (Bulletin of Engineering Geology and the Environment, 2022)

Identification and characterization of 76 SNP markers in the large-scale loach (Paramisgurnus dabryanus) by using SLAF sequencing - Jianjun Fu; Shunpeng Wan; Wenbin Zhu; Lanmei Wang; Mingkun Luo; Xianhu Zheng; Zaijie Dong (Conservation Genetics Resources, 2022)

Efficient seismic data reconstruction based on Geman function minimization - Yan-Yan Li; Li-Hua Fu; Wen-Ting Cheng; Xiao Niu; Wan-Juan Zhang (Applied Geophysics, 2022)

Interaction between organic matter and tetracycline in river sediments in cold regions - Changyong Wu; Rui Tang; Huiqi Li; Xiang Liu; Liya Fu; Yin Yu; Chunli Wan (Environmental Science and Pollution Research, 2022)

Temporal Trend of Polycyclic Aromatic Hydrocarbons in Atmosphere: A Case Study within 24 h after Snowfall - Hui-Ze Fan; Fu-Jie Zhu; Wan-Li Ma (Bulletin of Environmental Contamination and Toxicology, 2022)

Surface wind and vertical extent features of the explosive cyclones in the Northern Hemisphere based on the ERA‐I reanalysis data - Li‐Zhi Jiang; Shen‐Ming Fu; Jian‐Hua Sun; Rui Fu; Wan‐Li Li; Si‐Xiong Zhao; Hui Wang (International Journal of Climatology, 2022)
Although explosive cyclones (ECs) have long been a focus of research, there remains a lack of knowledge of the statistical characteristics of their associated maximum surface winds and vertical extents. This study fills this gap by conducting a targeted statistical analysis of ECs in the Northern Hemisphere using the ERA‐I reanalysis data during a 40‐year period. Some new findings are obtained: (a) The average location of formation of ECs undergoes a notable westward and equatorward shift from September to April in the next year which is consistent with the location variations of sea surface temperature's strong gradients in subtropical regions. (b) Extreme ECs with a deepening rate more than 2.0 Bergeron or with a longer lifespan more than 10 days tend to have a larger occurrence number over the Northern Atlantic Ocean than over the Northern Pacific. (c) The maximum surface wind associated with an EC tends to appear between the EC reaching its maximum deepening rate and reaching its minimum central pressure. (d) The northeastern quadrant of ECs accounts for the highest proportion of maximum surface wind and strongest wind speed, as the baroclinic energy conversion is generally strongest in this quadrant. (e) Over 60% of ECs belong to a type of vertically deep cyclone (ECs' top levels show close relationship to ascending motions within their central regions), and they tend to reach their maximum vertical extent around the time when they reach their minimum central pressures. (f) The highest top levels of ECs exhibit an overall upward extending trend as their minimum central pressure decreases or their maximum deepening rate increases.

Different Changing Patterns of Three NOS–NO System Activities after Ischemia–Reperfusion in Rabbit with AMI - Jun Zhang; Chao Chen; Fengpeng Li; Guangren Gao; Jinguo Fu; Heping Niu; Kai Yu; Lei Wang; Run Guo; Yanfang Wan; Zhanfeng Ma; Qianyu Zhang; et al. (Cell Biochemistry and Biophysics, 2021)

Correction to: Considerations for Updates to ICH Q1 and Q5C Stability Guidelines: Embracing Current Technology and Risk Assessment Strategies - Megan E. McMahon; Alexander Abbott; Yelizaveta Babayan; Jenny Carhart; Chi-wan Chen; Elke Debie; Mingkun Fu; Cherokee Hoaglund-Hyzer; Andrew Lennard; Hanlin Li; Tony Mazzeo; Lori McCaig; et al. (The AAPS Journal, 2021)

Considerations for Updates to ICH Q1 and Q5C Stability Guidelines: Embracing Current Technology and Risk Assessment Strategies - Megan E. McMahon; Alexander Abbott; Yelizaveta Babayan; Jenny Carhart; Chi-wan Chen; Elke Debie; Mingkun Fu; Cherokee Hoaglund-Hyzer; Andrew Lennard; Hanlin Li; Tony Mazzeo; Lori McCaig; et al. (The AAPS Journal, 2021)

Differential metabolism-associated gene expression of duck pancreatic cells in response to two strains of duck hepatitis A virus type 1 - Zhen Chen; Shao-hua Shi; Yu Huang; Cui-qin Huang; Rong-chang Liu; Long-fei Cheng; Guang-hua Fu; Hong-mei Chen; Chun-he Wan; Qiu-ling Fu (Archives of Virology, 2021)
Several outbreaks of duck hepatitis A virus type 1 (DHAV-1), which were characterized by yellow coloration and hemorrhage in pancreatic tissues, have occurred in China. The causative agent is called pancreatitis-associated DHAV-1. The mechanisms involved in pancreatitis-associated DHAV-1 infection are still unclear. Transcriptome analysis of duck pancreas infected with classical-type DHAV-1 and pancreatitis-associated DHAV-1 was carried out. Deep sequencing with Illumina-Solexa resulted in a total of 53.9 Gb of clean data from the cDNA library of the pancreas, and a total of 29,597 unigenes with an average length of 993.43 bp were generated by de novo sequence assembly. The expression levels of D-3-phosphoglycerate dehydrogenase, phosphoserine aminotransferase, and phosphoserine phosphatase, which are involved in glycine, serine, and threonine metabolism pathways, were significantly downregulated in ducks infected with pancreatitis-associated DHAV-1 compared with those infected with classical-type DHAV-1. These findings provide information regarding differences in expression levels of metabolism-associated genes between ducks infected with pancreatitis-associated DHAV-1 and those infected with classical-type DHAV-1, indicating that intensive metabolism disorders may contribute to the different phenotypes of DHAV-1-infection.

RETRACTED ARTICLE: Two New Coordination Polymers: Selective Detection of Cu(II) Ion and Treatment Activity on Inner Ear Damage - Jing Liu; Wan-Dong She; Fu-Sen Wang; Qing Zhou (Journal of Fluorescence, 2021)

Enhanced degradation of reactive brilliant red X-3B by photocatalysis integrated with micro-electrolysis - Gong Cheng; Yibo Zhang; Lei Sun; Jing Wan; Zhang Li; Chenyuan Dang; Jie Fu (Environmental Science and Pollution Research, 2021)

Genetic mapping reveals BjRf as a candidate gene controlling fertility restoration of the oxa CMS in Brassica juncea - Qiqi Cheng; Peijie Yao; Hui Li; Yiming Han; Kejing Xu; Shuangping Heng; Tingdong Fu; Zhengjie Wan (Theoretical and Applied Genetics, 2021)

Concentration determination of gold nanoparticles by flame atomic absorption spectrophotometry - Yuhong Fu; Quan Wan; Zonghua Qin; Shanshan Li; Sen Li; Ji Wang; Wei Zhang (Acta Geochimica, 2021)

Seasonal variation of nitrogen biogeochemical processes constrained by nitrate dual isotopes in cascade reservoirs, Southwestern China - Sai-Nan Chen; Fu-Jun Yue; Xiao-Long Liu; Jun Zhong; Yuan-Bi Yi; Wan-Fa Wang; Yulin Qi; Hua-Yun Xiao; Si-Liang Li (Environmental Science and Pollution Research, 2021)

A new chlorine-containing iridoid glycoside from Plantago maxima - Liang-Liang Ma; Lu-Lu Wang; Yue-Feng Zhang; Xiang-Fu Jiang; Xin-Liu Zhu; Ke Pan; Chuan-Xing Wan; Zhong-Bo Zhou (Natural Product Research, 2021)

Comparisons of Subjective and Objective Measures of Free-Living Daily Physical Activity and Sedentary Behavior in College Students - Ya-Wen Hsu; Chia-Chang Liu; Yen-Jung Chang; Yi-Ju Tsai; Wan-Chi Tsai; You Fu (Journal of Science in Sport and Exercise, 2021)

Comparative proteomic analysis of parasitic loranthus seeds exposed to dehydration stress - Limei Pan; Lingyun Wan; Lili He; Lisha Song; Hairong Long; Xiaowen Ji; Ni Jiang; Juan Huo; Shugen Wei; Jine Fu (Plant Biotechnology Reports, 2021)

Virtual reference station-based computerized ionospheric tomography - Weijun Lu; Guanyi Ma; Qingtao Wan; Jinghua Li; Xiaolan Wang; Weizheng Fu; Takashi Maruyama (GPS Solutions, 2021)
In computerized ionospheric tomography (CIT) with ground-based GNSS, the voxels without satellite-receiver ray traversing cannot be reconstructed directly. We present a CIT algorithm based on virtual reference stations (VRSs), called VRS–CIT, to decrease the number of unilluminated voxels and improve the precision of the estimated ionospheric electron density (IED). The VRSs are set at the nodes of grids with a 0.5° × 0.5° resolution in longitude and latitude. We generate the virtual observations with the observations from nearby six or three stations selected according to azimuths and distances. The generation utilizes multi-quadric surface fitting with six stations and triangular linear interpolation with three stations. With the virtual observations added, the IED distribution is reconstructed by the multiplicative algebraic reconstruction technique with the initial values obtained from IRI-2016. The performance of VRS–CIT is examined by using the data from 127 GNSS stations located in 24–46° N and 122–146° E to derive the IED every 30 min. The study focuses on April 29, 2014, with the adaptability of VRS–CIT analyzed by 12 days, evenly distributed around equinoxes and solstices of 2014. The accuracy of the virtual observation is about 1 TECU. Comparing to that derived from CIT with only real observations, the unsolvability of VRS–CIT declined by 4–12% for the whole region, and for the main area, the improvement can be up to 70%. Taking two IED profiles from radio occultation as reference measurements, the mean absolute error (MAE) of IED by VRS–CIT decreases by 6.88% and 8.43%, respectively. Comparing with slant total electron content (STEC) extracted from five additional GNSS stations, the MAE and the root mean square error of the estimated STEC can be reduced up to 17.24% and 33.81%, respectively.

Climate‐induced nonlinearity in pelagic communities and non‐stationary relationships with physical drivers in the Kuroshio ecosystem - Shuyang Ma; Yongjun Tian; Caihong Fu; Haiqing Yu; Jianchao Li; Yang Liu; Jiahua Cheng; Rong Wan; Yoshiro Watanabe (Fish and Fisheries, 2021)
Climate‐induced nonlinearity in biological variability and non‐stationary relationships with physical drivers are crucial to understand responses of marine organisms to climate variability. These phenomena have raised concerns in the northeastern North Pacific, but are out of the spotlight in the northwestern North Pacific in spite of potential implications for this productive system under increased climate variability. Pelagic communities in the Kuroshio ecosystem have both ecological and economic importance. However, patterns of climate‐induced nonlinearity in pelagic communities are not well understood, and existence of non‐stationarity in their relationships with physical drivers remains obscure. Here, we compile large numbers of climatic, oceanic and biological long‐term time‐series data and employ diverse statistical techniques to reveal such climate‐induced nonlinearity and non‐stationarity. Results show that pelagic communities in the Tsushima and Pacific areas (major areas in the Kuroshio ecosystem) had regime shifts in the late 1990s and late 1980s, respectively. Winter sea surface temperatures in the Kuroshio Current path and in the eastern part of East China Sea, which are respectively affected by the Kuroshio Current and Siberian High, correlate with dominant variability patterns in their pelagic communities. Furthermore, non‐stationarity was identified with threshold years in the 1990s in the Tsushima area and in the 1980s in the Pacific area as a possible result of the declined variances in the Siberian High and Aleutian Low, respectively. Our findings provide insights on spatial differentiation of climate‐induced nonlinearity and non‐stationarity, which are valuable for the management of pelagic communities in the northwestern North Pacific under changing climatic conditions.

Fine-mapping of the BjPur gene for purple leaf color in Brassica juncea - Shuangping Heng; Qiqi Cheng; Tian Zhang; Xujia Liu; Hao Huang; Peijie Yao; Zhixin Liu; Zhengjie Wan; Tingdong Fu (Theoretical and Applied Genetics, 2020)

Experimental study of suffusion characteristics within granite residual soil controlling inflow velocity - Weiping Liu; Shaofeng Wan; Xiaoyan Luo; Mingfu Fu (Arabian Journal of Geosciences, 2020)

Growth and Distribution of Amphioctopus fangsiao (d’Orbigny, 1839–1841) in Haizhou Bay, Yellow Sea - Yumeng Pang; Yongjun Tian; Caihong Fu; Yiping Ren; Rong Wan (Journal of Ocean University of China, 2020)

KIF3A regulates the Wnt/β-catenin pathway via transporting β-catenin during spermatogenesis in Eriocheir sinensis - Ya-Jing Liang; Jia-Hao Ni; Lan-Min Wang; Fu-Qing Tan; Wan-Xi Yang (Cell and Tissue Research, 2020)

miR-346-3p promotes osteoclastogenesis via inhibiting TRAF3 gene - Yingji Mao; Yu Chen; Yingxiao Fu; Jingjing Guan; Mengxiang Liang; Yansong Zhu; Fugen Yang; Feixiang Li; Zhe Zhang; Chuanfeng Wan; Pinghui Zhou (In Vitro Cellular & Developmental Biology - Animal, 2020)

A new metagenome binning method based on gene uniqueness - Yulin Kang; Cheng Wan; Sifen Lu; Zhehan Fu; Antony K. Chen; Zuhong Lu (Genes & Genomics, 2020)

Genome-Wide Analysis of LAZ1 Gene Family from Maize - Bing Liang Liu; Hao Qiang Yu; Qian Wen; Feng Ling Fu; Wan Chen Li (Journal of Plant Growth Regulation, 2020)

The effect of pH on the sorption of gold nanoparticles on illite - Yuhong Fu; Quan Wan; Zonghua Qin; Xin Nie; Wenbin Yu; Shanshan Li (Acta Geochimica, 2020)

Identification of rs11615992 as a novel regulatory SNP for human P2RX7 by allele-specific expression - Tao Peng; Li Zhong; Jing Gao; Zhu Wan; Wei-Ping Fu; Chang Sun (Molecular Genetics and Genomics, 2020)

Experimental study of subsurface erosion in granitic under the conditions of different soil column angles and flow discharges - Weiping Liu; Shaofeng Wan; Faming Huang; Xiaoyan Luo; Mingfu Fu (Bulletin of Engineering Geology and the Environment, 2019)

Interception of sulfate deposition from a closed canopy to a forest gap edge canopy in a subalpine dragon spruce plantation - Yu Zhang; Fu-zhong Wu; Bo Tan; Zhen-feng Xu; Han Li; Jun-cheng Liu; Hai-rong Zhao; Si-yi Tan; Cheng-ming You; Wan-qin Yang (Journal of Mountain Science, 2019)

The effects of simulated deposited nitrogen on nutrient dynamics in decomposing litters across a wide quality spectrum using a 15N tracing technique - Xue-Min Ye; Yang Zhang; Fu-Sheng Chen; G. Geoff Wang; Xiang-Min Fang; Xiao-Fan Lin; Song-Ze Wan; Ping He (Plant and Soil, 2019)

Effects of different potassium fertilizers on cadmium uptake by three crops - Kang Wang; Guiping Fu; Yao Yu; Yanan Wan; Zhe Liu; Qi Wang; Jingsuo Zhang; Huafen Li (Environmental Science and Pollution Research, 2019)

Effect of freeze-thaw cycles on uniaxial mechanical properties of cohesive coarse-grained soils - Yong-long Qu; Guo-liang Chen; Fu-jun Niu; Wan-kui Ni; Yan-hu Mu; Jing Luo (Journal of Mountain Science, 2019)

Comprehensive Assessment and Rechecking of Rainfall Threshold for Flash Floods Based on the Disaster Information - Wenlin Yuan; Lei Fu; Qianyu Gao; Fang Wan (Water Resources Management, 2019)

The Inhibitory Effects of Nitrogen Deposition on Asymbiotic Nitrogen Fixation are Divergent Between a Tropical and a Temperate Forest - Mianhai Zheng; Wei Zhang; Yiqi Luo; Shiqiang Wan; Shenglei Fu; Senhao Wang; Nan Liu; Qing Ye; Junhua Yan; Bi Zou; Chengliang Fang; Yuxi Ju; et al. (Ecosystems, 2019)

Population Genetics of Calotropis gigantea, a Medicinal and Fiber Resource Plant, as Inferred from Microsatellite Marker Variation in two Native Countries - Md. Rabiul Islam; Zhi-Zhong Li; Andrew W. Gichira; Mohammad Nur Alam; Peng-Cheng Fu; Guang-Wan Hu; Qing-Feng Wang; Ling-Yun Chen (Biochemical Genetics, 2019)

The China Multi-Model Ensemble Prediction System and Its Application to Flood-Season Prediction in 2018 - Hong-Li Ren; Yujie Wu; Qing Bao; Jiehua Ma; Changzheng Liu; Jianghua Wan; Qiaoping Li; Xiaofei Wu; Ying Liu; Ben Tian; Joshua-Xiouhua Fu; Jianqi Sun (Journal of Meteorological Research, 2019)

Nitrogen deposition effect on forest litter decomposition is interactively regulated by endogenous litter quality and exogenous resource supply - Fu-Sheng Chen; G. Geoff Wang; Xiang-Min Fang; Song-Ze Wan; Yang Zhang; Chao Liang (Plant and Soil, 2019)

Isolation and characterization of duck adenovirus 3 circulating in China - Shaohua Shi; Rongchang Liu; Chunhe Wan; Longfei Cheng; Zhen Chen; Guanghua Fu; Hongmei Chen; Qiuling Fu; Yu Huang (Archives of Virology, 2019)

Cytotoxic indole alkaloids from Nauclea orientalis - Yan-Ping Liu; Peng-Kun Ju; Jin-Tao Long; Liang Lai; Wan-Hui Zhao; Chao Zhang; Zhi-Jie Zhang; Yan-Hui Fu (Natural Product Research, 2018)

Association mapping of salt tolerance traits at germination stage of rapeseed (Brassica napus L.) - Heping Wan; Yinke Wei; Jiali Qian; Yunlei Gao; Jing Wen; Bin Yi; Chaozhi Ma; Jinxing Tu; Tingdong Fu; Jinxiong Shen (Euphytica, 2018)

Bioactive furanocoumarins from the stems and leaves of Clausena hainanensis - Yan-Lei Ma; Chao Zhang; Wan-Hui Zhao; Shi Shi; Dan-Nv He; Pan Zhang; Xiao-Hong Liu; Ting-Ting Han; Yan-Hui Fu; Yan-Ping Liu (Natural Product Research, 2018)

Effects of normoxic and hypoxic exercise training on the bactericidal capacity and subsequent apoptosis of neutrophils in sedentary men - Yi-Ching Chen; Wan-Yu Chou; Tieh-Cheng Fu; Jong-Shyan Wang (European Journal of Applied Physiology, 2018)

The Sesuvium portulacastrum Plasma Membrane Na+/H+ Antiporter SpSOS1 Complemented the Salt Sensitivity of Transgenic Arabidopsis sos1 Mutant Plants - Yang Zhou; Xiaochang Yin; Shumin Wan; Yanping Hu; Qing Xie; Ruimei Li; Baibi Zhu; Shaoping Fu; Jianchun Guo; Xingyu Jiang (Plant Molecular Biology Reporter, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Isolation and identification of bovine nasopharyngeal mucosal epithelial cells and establishment of cell models of acute infection by foot-and-mouth disease virus - Wan-fu Bai; Lu Li; Ting Zhang; Xiao-hu Su; Yong-wei Wang; Bing-wu Zhao; Tao Zhang; Huan-min Zhou (In Vitro Cellular & Developmental Biology - Animal, 2018)

Application of the Hybrid Artificial Neural Network Coupled with Rolling Mechanism and Grey Model Algorithms for Streamflow Forecasting Over Multiple Time Horizons - Zaher Mundher Yaseen; Minglei Fu; Chen Wang; Wan Hanna Melini Wan Mohtar; Ravinesh C. Deo; Ahmed El-shafie (Water Resources Management, 2018)

Interaction network of core ABA signaling components in maize - Ying-Ge Wang; Feng-Ling Fu; Hao-Qiang Yu; Tao Hu; Yuan-Yuan Zhang; Yi Tao; Jian-Kang Zhu; Yang Zhao; Wan-Chen Li (Plant Molecular Biology, 2018)

Morphological and genetic characterization of a new cytoplasmic male sterility system (oxa CMS) in stem mustard (Brassica juncea) - Shuangping Heng; Sansan Liu; Chunxiu Xia; HongYu Tang; Fei Xie; Tingdong Fu; Zhengjie Wan (Theoretical and Applied Genetics, 2018)

Lipid accumulation and anti-rotifer robustness of microalgal strains isolated from Eastern China - Cheng Yuan; Yan-Lin Zheng; Wan-Lu Zhang; Ru He; Yong Fan; Guang-Rong Hu; Fu-Li Li (Journal of Applied Phycology, 2017)

Role of early environmental enrichment on the social dominance tube test at adulthood in the rat - Wen-Yu Cao; Zhao-Lan Hu; Yang Xu; Wen-Juan Zhang; Fu-Lian Huang; Xiao-Qing Qiao; Yan-Hui Cui; Wei Wan; Xue-qin Wang; Dan Liu; Ru-Ping Dai; Fang Li; et al. (Psychopharmacology, 2017)

An analysis of patents for anesthetic laryngoscopes - Cheng-dong Ji; Xin Pan; Yuan-chang Xiong; Xuan Guo; Shu-wen Qian; Chang Xu; Qiang-qiang Fu; Zhi-ping Yang; Yu Ma; Yue-zhu Wan (Journal of Zhejiang University-SCIENCE B, 2017)

Long-term fertilization increases soil nutrient accumulations but decreases biological activity in navel orange orchards of subtropical China - Song-Ze Wan; Han-Jiao Gu; Qing-Pei Yang; Xiao-Fei Hu; Xiang-Min Fang; Anand Narain Singh; Fu-Sheng Chen (Journal of Soils and Sediments, 2017)

KIFC1 and myosin Va: two motors for acrosomal biogenesis and nuclear shaping during spermiogenesis of Portunus trituberculatus - Dan-Dan Ma; Meng-Ying Pan; Cong-Cong Hou; Fu-Qing Tan; Wan-Xi Yang (Cell and Tissue Research, 2017)

Associations of rs3740677 within GAB2 Gene with LOAD in Chinese Han Population - Jing-Yu Zheng; Hui-Fu Wang; Yu Wan; Meng-Shan Tan; Chen-Chen Tan; Lin Tan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Effects of HLA-DRB1/DQB1 Genetic Variants on Neuroimaging in Healthy, Mild Cognitive Impairment, and Alzheimer’s Disease Cohorts - Zi-Xuan Wang; Hui-Fu Wang; Lin Tan; Jinyuan Liu; Yu Wan; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Genetic Association of HLA Gene Variants with MRI Brain Structure in Alzheimer’s Disease - Zi-Xuan Wang; Yu Wan; Lin Tan; Jinyuan Liu; Hui-Fu Wang; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Association of DISC1 Polymorphisms with Late-Onset Alzheimer’s Disease in Northern Han Chinese - Xiao-Yan Zhang; Hui-Fu Wang; Meng-Shan Tan; Yu Wan; Ling-Li Kong; Zhan-Jie Zheng; Chen-Chen Tan; Wei Zhang; Zi-Xuan Wang; Lin Tan; Teng Jiang; Lan Tan; et al. (Molecular Neurobiology, 2017)

SORL1 Is Associated with the Risk of Late-Onset Alzheimer’s Disease: a Replication Study and Meta-Analyses - Cheng-Cheng Zhang; Hui-Fu Wang; Meng-Shan Tan; Yu Wan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Lin Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

A Missense Variant in TREML2 Reduces Risk of Alzheimer’s Disease in a Han Chinese Population - Teng Jiang; Yu Wan; Jun-Shan Zhou; Meng-Shan Tan; Qing Huang; Xi-Chen Zhu; Huan Lu; Hui-Fu Wang; Qi Chen; Lin Tan; Ying-Dong Zhang; Lan Tan; et al. (Molecular Neurobiology, 2017)

Computational investigation on inhibition mechanism of BRAFV600E by Vemurafenib (PLX4032) and its analogue PLX4720 - XiaoYun Wu; Yu Fu; YuanYuan Wang; ShanHe Wan; JiaJie Zhang (Medicinal Chemistry Research, 2017)

The Impact of UNC5C Genetic Variations on Neuroimaging in Alzheimer’s Disease - Jia-Hao Sun; Hui-Fu Wang; Xi-Chen Zhu; Wan-Jiang Yu; Chen-Chen Tan; Teng Jiang; Meng-Shan Tan; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2016)

Synthesis and antimicrobial evaluation of 3-substituted-imine-6-hydroxy-benzofuran derivatives - Wan He; Buzhe Xu; Jian Bao; Xinxian Deng; Wenlu Liu; Yong Zhang; Faqin Jiang; Lei Fu (Medicinal Chemistry Research, 2016)

Wnt5a mediated canonical Wnt signaling pathway activation in orthodontic tooth movement: possible role in the tension force-induced bone formation - Hai-Di Fu; Bei-Ke Wang; Zi-Qiu Wan; Heng Lin; Mao-Lin Chang; Guang-Li Han (Journal of Molecular Histology, 2016)

Autologous Bone Marrow Mononuclear Cell Transplantation Delays Progression of Carotid Atherosclerosis in Rabbits - Kefei Cui; Xiao Ma; Lie Yu; Chao Jiang; Chao Fu; Xiaojie Fu; Xiaofang Yu; Yuanjing Huang; Suyun Hou; Caifeng Si; Zhengguang Chen; Jing Yu; et al. (Molecular Neurobiology, 2016)

Endo-1,4-β-glucanase gene involved into the rapid elongation of Phyllostachys heterocycla var. pubescens - Ming-Bing Zhou; Ying Zheng; Zhi-Gang Liu; Xiang-Wan Xia; Ding-Qin Tang; Ying Fu; Ming Chen (Trees, 2016)

Two new triterpenoid glycosides from the stems of Camellia oleifera Abel - Qing-Wei Yan; Hui-Zheng Fu; Yue-Hua Luo; Guo-Ping Zhou; Kai-Hua Wan; Rui-Jian Zhong (Natural Product Research, 2016)

The Syntheses, Structures, Fluorescence Properties and Biological Activity of two Novel Zinc(II) Complexes Controlled by the Tripodal Imidazole Ligand - En-Jun Gao; Shaozhong Zhang; Yang Meng; Fu-Chen Zhao; Xiao-Yu Ma; Hai-Tao Jin; Si-Jia Liu; Jing Ge; Ya-Guang Sun; Wan-zhong Zhang; Ming-Chang Zhu (Journal of Fluorescence, 2016)

Piromelatine ameliorates memory deficits associated with chronic mild stress-induced anhedonia in rats - Wan Fu; Heng Xie; Moshe Laudon; Shouhong Zhou; Shaowen Tian; Yong You (Psychopharmacology, 2016)

Fine mapping of barley locus Rps6 conferring resistance to wheat stripe rust - Kun Li; Joshua Hegarty; Chaozhong Zhang; Anmin Wan; Jiajie Wu; Gina Brown Guedira; Xianming Chen; María Muñoz-Amatriaín; Daolin Fu; Jorge Dubcovsky (Theoretical and Applied Genetics, 2016)

Ectomycorrhizae of Tuber huidongense and T. liyuanum with Castanea mollissima and Pinus armandii - Shan-Ping Wan; Fu-Qiang Yu; Li Tang; Ran Wang; Yun Wang; Pei-Gui Liu; Xiang-Hua Wang; Yi Zheng (Mycorrhiza, 2016)

Sunfleck limits the small-scale distribution of endangered Kingdonia uniflora in the natural habitat of subalpine forest proved by its photosynthesis - Chen-Guang Zhang; Xiao Liu; Yi-Lei Fan; Mao Wang; Yong-Fu Chai; Peng-Cheng Wan; Ya-Min Wang; Ming Yue (Acta Physiologiae Plantarum, 2016)

MicroRNA let-7g cooperates with interferon/ribavirin to repress hepatitis C virus replication - Wen-Wen Chou; Chung-Feng Huang; Ming-Lun Yeh; Yi-Shan Tsai; Ming-Yen Hsieh; Ching-I Huang; Jee-Fu Huang; Pei-Chien Tsai; Edward Hsi; Suh-Hang Hank Juo; Wei-Lun Tsai; Wan-Long Chuang; et al. (Journal of Molecular Medicine, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

The potential function of prohibitin during spermatogenesis in Chinese fire-bellied newt Cynops orientalis - Jia-Min Jin; Cong-Cong Hou; Fu-Qing Tan; Wan-Xi Yang (Cell and Tissue Research, 2016)

Different Responses of an Invasive Clonal Plant Wedelia trilobata and its Native Congener to Gibberellin: Implications for Biological Invasion - Zhi-Cong Dai; Wei Fu; Shan-Shan Qi; De-Li Zhai; Si-Chong Chen; Ling-Yun Wan; Ping Huang; Dao-Lin Du (Journal of Chemical Ecology, 2016)

Comparative analysis of transcriptional profiles of retinoic-acid-induced gene I-like receptors and interferons in seven tissues from ducks infected with avian Tembusu virus - Guanghua Fu; Cuiteng Chen; Yu Huang; Longfei Cheng; Qiuling Fu; Chunhe Wan; Shaohua Shi; Hongmei Chen; Wei Liu (Archives of Virology, 2016)

Overexpression of a phospholipase Dα gene from Ammopiptanthus nanus enhances salt tolerance of phospholipase Dα1-deficient Arabidopsis mutant - Hao Qiang Yu; Tai Ming Yong; Hong Jie Li; Yan Ping Liu; Shu Feng Zhou; Feng Ling Fu; Wan Chen Li (Planta, 2015)

Characterization and classification of one new cytoplasmic male sterility (CMS) line based on morphological, cytological and molecular markers in non-heading Chinese cabbage (Brassica rapa L.) - Shuangping Heng; Dianyi Shi; Zhenhua Hu; Tao Huang; Jinping Li; Liyan Liu; Chunxiu Xia; Zhenzhen Yuan; Yuejin Xu; Tingdong Fu; Zhengjie Wan (Plant Cell Reports, 2015)

Cloning and functional validation of molybdenum cofactor sulfurase gene from Ammopiptanthus nanus - Hao Qiang Yu; Yuan Yuan Zhang; Tai Ming Yong; Yan Ping Liu; Shu Feng Zhou; Feng Ling Fu; Wan Chen Li (Plant Cell Reports, 2015)

Clipping alters the response of biomass production to experimental warming: A case study in an alpine meadow on the Tibetan Plateau, China - Gang Fu; Wei Sun; Cheng-Qun Yu; Xian-Zhou Zhang; Zhen-Xi Shen; Yun-Long Li; Peng-Wan Yang; Nan Zhou (Journal of Mountain Science, 2015)

Paroxysmal kinesigenic dyskinesia and myotonia congenita in the same family: coexistence of a PRRT2 mutation and two CLCN1 mutations - Hong-Fu Li; Wan-Jin Chen; Wang Ni; Zhi-Ying Wu (Neuroscience Bulletin, 2014)

Expression Profile of Maize MicroRNAs Corresponding to Their Target Genes Under Drought Stress - Ying-Ge Wang; Ming An; Shu-Feng Zhou; Yue-Hui She; Wan-Chen Li; Feng-Ling Fu (Biochemical Genetics, 2014)

Accumulation of FLT3+ CD11c+ dendritic cells in psoriatic lesions and the anti-psoriatic effect of a selective FLT3 inhibitor - Heng-Xiu Yan; Wei-Wei Li; Yan Zhang; Xia-Wei Wei; Li-Xin Fu; Guo-Bo Shen; Tao Yin; Xiu-Ying Li; Hua-Shan Shi; Yang Wan; Qing-Yin Zhang; Jiong Li; et al. (Immunologic Research, 2014)

The population genomic landscape of human genetic structure, admixture history and local adaptation in Peninsular Malaysia - Lian Deng; Boon Peng Hoh; Dongsheng Lu; Ruiqing Fu; Maude E. Phipps; Shilin Li; Ab Rajab Nur-Shafawati; Wan Isa Hatin; Endom Ismail; Siti Shuhada Mokhtar; Li Jin; Bin Alwi Zilfalil; et al. (Human Genetics, 2014)

A new naphthalene glycoside from the sponge-derived fungus Arthrinium sp. ZSDS1-F3 - Jun-Feng Wang; Fu-Quan Xu; Zhen Wang; Xin Lu; Jun-Ting Wan; Bin Yang; Xue-Feng Zhou; Tian-Yu Zhang; Zheng-Chao Tu; Yonghong Liu (Natural Product Research, 2014)

miR-145 Inhibits Migration and Invasion of Glioma Stem Cells by Targeting ABCG2 - Lei Shi; Zhimin Wang; Guan Sun; Yi Wan; Jun Guo; Xingli Fu (NeuroMolecular Medicine, 2014)

Emodin elicits cytotoxicity in human lung adenocarcinoma A549 cells through inducing apoptosis - Wing-Yan Li; Yam-Fung Ng; Huan Zhang; Zi-Dong Guo; De-Jian Guo; Yiu-Wa Kwan; George Pak-Heng Leung; Simon Ming-Yuen Lee; Peter Hoi-Fu Yu; Shun-Wan Chan (Inflammopharmacology, 2014)

Molecular characterization and expression analysis of a KIFC1-like kinesin gene in the testis of Eumeces chinensis - Jian-Rao Hu; Mei Liu; Da-Hui Wang; Yan-Jun Hu; Fu-Qing Tan; Wan-Xi Yang (Molecular Biology Reports, 2013)

Regulation of paracellular permeability: factors and mechanisms - Yan-Jun Hu; Yi-Dong Wang; Fu-Qing Tan; Wan-Xi Yang (Molecular Biology Reports, 2013)

Better environmental data may reverse conclusions about niche‐ and dispersal‐based processes in community assembly - Li-Wan Chang; David Zelený; Ching-Feng Li; Shau-Ting Chiu; Chang-Fu Hsieh (Ecology, 2013)
Variation partitioning of species composition into components explained by environmental and spatial variables is often used to identify a signature of niche‐ and dispersal‐based processes in community assembly. Such interpretation, however, strongly depends on the quality of the environmental data available. In recent studies conducted in forest dynamics plots, the environment was represented only by readily available topographical variables. Using data from a subtropical broad‐leaved dynamics plot in Taiwan, we focus on the question of how would the conclusion about importance of niche‐ and dispersal‐based processes change if soil variables are also included in the analysis. To gain further insight, we introduced multiscale decomposition of a pure spatial component [c] in variation partitioning. Our results indicate that, if only topography is included, dispersal‐based processes prevail, while including soil variables reverses this conclusion in favor of niche‐based processes. Multiscale decomposition of [c] shows that if only topography was included, broad‐scaled spatial variation prevails in [c], indicating that other as yet unmeasured environmental variables can be important. However, after also including soil variables this pattern disappears, increasing importance of meso‐ and fine‐scaled spatial patterns indicative of dispersal processes.

RNA interference-mediated resistance to maize dwarf mosaic virus - Zhi-Yong Zhang; Ying-Ge Wang; Xiao-Juan Shen; Lei Li; Shu-Feng Zhou; Wan-Chen Li; Feng-Ling Fu (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Response of ecosystem respiration to experimental warming and clipping at daily time scale in an alpine meadow of tibet - Gang Fu; Zhen-xi Shen; Xian-zhou Zhang; Cheng-qun Yu; Yu-ting Zhou; Yun-long Li; Peng-wan Yang (Journal of Mountain Science, 2013)

Morphological and molecular cytogenetic characterization of partial octoploid Tritileymus - Jing Wang; Xin-Hong Chen; Wan-Li Du; Ji-Xin Zhao; Jun Wu; Xue-Ni Cheng; Yu-Hui Pang; Qun-Hui Yang; Shu-Hui Liu; Jie Fu (Genetic Resources and Crop Evolution, 2013)

Development and identification of a wheat-Leymus mollis multiple alien substitution line - Ji-Xin Zhao; Wan-Li Du; Jun Wu; Xue-Ni Cheng; Yang Gao; Yu-Hui Pang; Xin-Hong Chen; Shu-Hui Liu; Qun-Hui Yang; Jie Fu (Euphytica, 2013)

A review of the anticancer and immunomodulatory effects of Lycium barbarum fruit - Wai-Man Tang; Enoch Chan; Ching-Yee Kwok; Yee-Ki Lee; Jian-Hong Wu; Chun-Wai Wan; Robbie Yat-Kan Chan; Peter Hoi-Fu Yu; Shun-Wan Chan (Inflammopharmacology, 2012)

The variation of tree beta diversity across a global network of forest plots - Miquel De Cáceres; Pierre Legendre; Renato Valencia; Min Cao; Li‐Wan Chang; George Chuyong; Richard Condit; Zhanqing Hao; Chang‐Fu Hsieh; Stephen Hubbell; David Kenfack; Keping Ma; et al. (Global Ecology and Biogeography, 2012)
Aims With the aim of understanding why some of the world's forests exhibit higher tree beta diversity values than others, we asked: (1) what is the contribution of environmentally related variation versus pure spatial and local stochastic variation to tree beta diversity assessed at the forest plot scale; (2) at what resolution are these beta‐diversity components more apparent; and (3) what determines the variation in tree beta diversity observed across regions/continents? Location World‐wide. Methods We compiled an unprecedented data set of 10 large‐scale stem‐mapping forest plots differing in latitude, tree species richness and topographic variability. We assessed the tree beta diversity found within each forest plot separately. The non‐directional variation in tree species composition among cells of the plot was our measure of beta diversity. We compared the beta diversity of each plot with the value expected under a null model. We also apportioned the beta diversity into four components: pure topographic, spatially structured topographic, pure spatial and unexplained. We used linear mixed models to interpret the variation of beta diversity values across the plots. Results Total tree beta diversity within a forest plot decreased with increasing cell size, and increased with tree species richness and the amount of topographic variability of the plot. The topography‐related component of beta diversity was correlated with the amount of topographic variability but was unrelated to its species richness. The unexplained variation was correlated with the beta diversity expected under the null model and with species richness. Main conclusions Because different components of beta diversity have different determinants, comparisons of tree beta diversity across regions should quantify not only overall variation in species composition but also its components. Global‐scale patterns in tree beta diversity are largely coupled with changes in gamma richness due to the relationship between the latter and the variation generated by local stochastic assembly processes.

An Effective Approach to Long-Term Optimal Operation of Large-Scale Reservoir Systems: Case Study of the Three Gorges System - Fang-Fang Li; Jia-Hua Wei; Xu-Dong Fu; Xin-Yu Wan (Water Resources Management, 2012)

Signal-purity-spectrum-based colored deconvolution - Guo-Fa Li; Geng-Xin Peng; Ying Yue; Wan-Li Wang; Yong-Fu Cui (Applied Geophysics, 2012)

Performance of Agasicles hygrophila (Coleoptera: Chrysomelidae), a biological control agent of invasive alligator weed, at low non-freezing temperatures - Jian-Ying Guo; Jian-Wei Fu; Xiao-Qing Xian; Ming-Yong Ma; Fang-Hao Wan (Biological Invasions, 2012)

Effect of temperature on fatty acid content in Vicia sativa - Zhuxin Mao; Hua Fu; Changgui Wan (Journal of Consumer Protection and Food Safety, 2012)

Analysis of 2,297 expressed sequence tags (ESTs) from a cDNA library of flax (Linum ustitatissimum L.) bark tissue - Song-Hua Long; Xin Deng; Yu-Fu Wang; Xiang Li; Rui-Qing Qiao; Cai-Sheng Qiu; Yuan Guo; Dong-Mei Hao; Wan-Qi Jia; Xin-Bo Chen (Molecular Biology Reports, 2012)

Molecular characterization of a KIF3B-like kinesin gene in the testis of Octopus tankahkeei (Cephalopoda, Octopus) - Ran Dang; Jun-Quan Zhu; Fu-Qing Tan; Wei Wang; Hong Zhou; Wan-Xi Yang (Molecular Biology Reports, 2012)

Molecular characterization of a KIF3A-like kinesin gene in the testis of the Chinese fire-bellied newt Cynops orientalis - Jian-Rao Hu; Na Xu; Fu-Qing Tan; Da-Hui Wang; Mei Liu; Wan-Xi Yang (Molecular Biology Reports, 2012)

A review of the pharmacological effects of Arctium lappa (burdock) - Yuk-Shing Chan; Long-Ni Cheng; Jian-Hong Wu; Enoch Chan; Yiu-Wa Kwan; Simon Ming-Yuen Lee; George Pak-Heng Leung; Peter Hoi-Fu Yu; Shun-Wan Chan (Inflammopharmacology, 2011)

Induction of Human Bone Marrow Mesenchymal Stem Cells Differentiation into Neural-Like Cells Using Cerebrospinal Fluid - Ying Ye; Yin-Ming Zeng; Mei-Rong Wan; Xian-Fu Lu (Cell Biochemistry and Biophysics, 2011)

Human insulin gene expressing with Bombyx mori multiple nucleopolyhedrovirus (BmMNPV) expression system - Wan-fu Yue; Fang Zhou; Jia-biao Hu; Enoch Y. Park; Joe Hull; Yun-gen Miao (World Journal of Microbiology and Biotechnology, 2011)

Three novel SNPs in the coding region of PPARγ gene and their associations with meat quality traits in cattle - Yue Yuan Fan; Lin Sen Zan; Chang Zhen Fu; Wan Qiang Tian; Hong Bao Wang; Yan Yan Liu; Ya Ping Xin (Molecular Biology Reports, 2011)

RNA Interference-Based Transgenic Maize Resistant to Maize Dwarf Mosaic Virus - Zhi-Yong Zhang; Feng-Ling Fu; Lin Gou; Han-Guang Wang; Wan-Chen Li (Journal of Plant Biology, 2010)

Effects of Bleomycin on microspore embryogenesis in Brassica napus and detection of somaclonal variation using AFLP molecular markers - Xinhua Zeng; Jing Wen; Zhengjie Wan; Bin Yi; Jinxiong Shen; Chaozhi Ma; Jinxing Tu; Tingdong Fu (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Cloning and Characterization of Functional Trehalose-6-Phosphate Synthase Gene in Maize - Wei Jiang; Feng-Ling Fu; Su-Zhi Zhang; Ling Wu; Wan-Chen Li (Journal of Plant Biology, 2010)

Quantification of silkworm coactivator of MBF1 mRNA by SYBR Green I real-time RT-PCR reveals tissue- and stage-specific transcription levels - Guang-li Li; Bhaskar Roy; Xing-hua Li; Wan-fu Yue; Xiao-feng Wu; Jian-mei Liu; Chuan-xi Zhang; Yun-gen Miao (Molecular Biology Reports, 2009)

Differential Expression of Serine/Threonine Protein Phosphatase Type-2C Under Drought Stress in Maize - Fu-Hua Li; Feng-Ling Fu; Li-Na Sha; Liang He; Wan-Chen Li (Plant Molecular Biology Reporter, 2009)

High-level expression of orange fluorescent protein in the silkworm larvae by the Bac-to-Bac system - Jian-mei Liu; Wan Chi Cheong David; Denis Tsz-Ming Ip; Xing-hua Li; Guang-li Li; Xiao-feng Wu; Wan-fu Yue; Chuan-xi Zhang; Yun-gen Miao (Molecular Biology Reports, 2009)

Silkworm powder containing manganese superoxide dismutase regulated the immunity and inhibited the growth of Hepatoma 22 cell in mice - Wan-Fu Yue; Wen Deng; Xing-Hua Li; Bhaskar Roy; Guang-Li Li; Jian-Mei Liu; Xiao-Feng Wu; Hong-Xiang Sun; Min-Li Yao; Wan Chi Cheong David; Yun-Gen Miao (Molecular Biology Reports, 2009)

Nonlinear cooperation of p53-ING1-induced bax expression and protein S-nitrosylation in GSNO-induced thymocyte apoptosis: a quantitative approach with cross-platform validation - Shaojin Duan; Lin Wan; Wenjiang J. Fu; Hong Pan; Qi Ding; Chang Chen; Peiwei Han; Xiaoyan Zhu; Liying Du; Hongxiao Liu; Yuxia Chen; Ximing Liu; et al. (Apoptosis, 2009)

Manganese superoxide dismutase expressed in silkworm larvae, Bombyx mori L enhances the NK activity and splenocyte proliferation against Sarcoma 180 tumor cells in vivo - Wan-Fu Yue; Min-Li Yao; Jian-Mei Liu; Guang-Li Li; Xing-Hua Li; Xiao-Feng Wu; Wen Deng; Hong-Xiang Sun; Ji-Yong Zhou; Chuan-Xi Zhang; Yun-Gen Miao (Molecular Biology Reports, 2009)

Effects of silkworm larvae powder containing manganese superoxide dismutase on immune activity of mice - Wan-Fu Yue; Jian-Mei Liu; Guang-Li Li; Xing-Hua Li; Xiao-Feng Wu; Jian-Tong Sun; Hong-Xiang Sun; Yun-Gen Miao (Molecular Biology Reports, 2008)

Population genetics of Ageratina adenophora using inter-simple sequence repeat (ISSR) molecular markers in China - Fu-Rong Gui; Fang-Hao Wan; Jian-Ying Guo (Plant Biosystems, 2008)

The concentrations, distribution and sources of PAHs in agricultural soils and vegetables from Shunde, Guangdong, China - Yong Tao Li; Fang Bai Li; Jun Jian Chen; Guo Yi Yang; Hong Fu Wan; Tian Bin Zhang; Xiao Duo Zeng; Jian Ming Liu (Environmental Monitoring and Assessment, 2008)

Genetic characterization of a new cytoplasmic male sterility system (hau) in Brassica juncea and its transfer to B. napus - Zhengjie Wan; Bing Jing; Jinxing Tu; Caozhi Ma; Jinxiong Shen; Bin Yi; Jing Wen; Tao Huang; Xianjun Wang; Tingdong Fu (Theoretical and Applied Genetics, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Enhanced induction of dendritic cell maturation and HLA-A*0201-restricted CEA-specific CD8+ CTL response by exosomes derived from IL-18 gene-modified CEA-positive tumor cells - Shengming Dai; Xiangyang Zhou; Baomei Wang; Qingqing Wang; Yangxin Fu; Taoyong Chen; Tao Wan; Yizhi Yu; Xuetao Cao (Journal of Molecular Medicine, 2006)

Identification of differentially expressed genes in Tetrahymena thermophila in response to dichlorodiphenyltrichloroethane (DDT) by suppression subtractive hybridization - Wei Miao; Ting Yu; Eduardo Orias; Mingliang Wan; Chenjie Fu (Environmental Microbiology, 2006)
Summary The insecticide dichlorodiphenyltrichloroethane (DDT) is persistent in the environment, and continues to cause health problems. Tetrahymena has potential as a model organism for assaying low levels of DDT and for analysing the mechanisms of its toxicity. We constructed the suppression subtractive hybridization library of T. thermophila exposed to DDT, and screened out 90 Expressed Sequence Tags whose expressions were significantly up‐ or downregulated with DDT treatment. From this, a series of important genes related to the DDT metabolism and detoxification were discovered, such as P450 gene, glutathione S‐transferase gene and sterol carrier protein 2 gene. Furthermore, their expressions under different concentrations of DDT treatment were detected by real‐time fluorescent quantitative PCR. The results show that Tetrahymena is a relevant and useful model organism for detecting DDT in the environment and for discovering biomarkers that can be used to develop specific bio‐reporters at the molecular and genomic levels.

Use of oligonucleotide fingerprinting and faecal DNA in identifying the distribution of the Chinese tiger (Panthera tigris amoyensis Hilzheimer) - Qiu-Hong Wan; Sheng-Guo Fang; Guo-Fu Chen; Zhang-Ming Wang; Ping Ding; Mu-Yuan Zhu; Kong-Shou Chen; Jiu-Hua Yu; Yue-Ping Zhao (Biodiversity and Conservation, 2003)